Plasma membrane H+-ATPase Pma1 regulates growth and virulence in Penicillium digitatum from citrus fruits involving iron homeostasis - Xinyue Lin; Huilin Kang; Shuzhen Yang; Gang Fan; Litao Peng; Hanyu Mu; Yanli Wang (Food Microbiology, 2026)

Hydrophobic sodium alginate/montmorillonite/CNTs composite hydrogel for simultaneous efficient solar-driven interfacial evaporation and suppressed salt deposition - Peng Liu; Xian Sun; Xiaobin Gu; Yunan Mu; Hongen Nian (Desalination, 2026)

Sequential doping strategy for all-biomass derived N/P co-doped biochar: Unraveling the divergent capture mechanisms in antibiotic removal - Chengyu Li; Qihang Wang; Kunxiang Zhang; Hong He; Lvxin Peng; Jun Mu (Bioresource Technology, 2026)

The multicopper ferroxidase Pdfet3 is essential for reductive iron assimilation, redox homeostasis, and virulence in Penicillium digitatum - Xinyue Lin; Shuzhen Yang; Hanyu Mu; Gang Fan; Litao Peng; Yanli Wang (Physiological and Molecular Plant Pathology, 2026)

Integrating scale-matched spatial scales into water scarcity risk screening in China - Jiayu Zhang; Dedi Liu; Jiabo Yin; Feng Yue; Jiaoyang Wang; Zhenyu Mu; Hanxu Liang; Zhilin Niu; Zhengbo Peng (Journal of Hydrology, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

Stepwise hydrolysis reduces allergenicity of α-lactalbumin through epitope removal and structural modulation - Qing Zhao; Guangqing Mu; Ruida Ma; Qi Sun; Peng Sun; Xiaomeng Wu; Fanhua Kong (Food Research International, 2026)

Unlocking the antioxidant potential of wheat gluten: structural transitions and peptide release driven by ultrasonication-assisted pH shifting - Peng Cheng; Xueying Song; Yihan Mu; Siliang Wu; Mouming Zhao; Guowan Su (Food Chemistry, 2026)

Transcriptional and translational optimization for enhancing β-galactosidase expression in bacillus subtilis - Zhuo Cheng; Qiuzi Peng; Jiajun Chen; Li Wan; Dawei Ni; Wei Xu; Penka Petrova; Kaloyan Petrov; Wenli Zhang; Wanmeng Mu (Food Bioscience, 2026)

Effects of fine particle migration caused by one wetting-drying cycle on desiccation micro-cracks in intact loess - Zhi-yuan He; Peng-hui Ma; Qing-yi Mu; Chao Zhou; Ke Mu; Zhi-jie Jia; Jian-bing Peng (Engineering Geology, 2026)

Photoperiod induces alterations in redox homeostasis, immune response, and responses to light stimulation in the red swamp crayfish (Procambarus clarkii) - Lang Zhang; Qi Bai; Yingchun Mu; Yali Yu; Liting Ye; Lu Qiao; Wenya Ji; Jie Peng; Meiping Lan; Ziwei Song; Yu Fang (Aquaculture, 2026)

Permafrost degradation amplifies infrastructure-related inequalities across the Qinghai-Tibet Plateau - Xinlong Du; Chunling Zhang; Yunjie Jia; Yuguo Wei; Jinyue Song; Mei Mu; Xiaoqing Peng; Zongxing Li; Peng Zhang; Lin Liu; Zhuoxuan Xia; Rongkun Liu; et al. (Global Environmental Change, 2026)

Reaction engineering of a solar chimney-driven honeycomb photocatalytic reactor for outdoor low concentration methane oxidation - Hanbing Xiong; Tingzhen Ming; Yongjia Wu; Liwen Mu; Renaud de Richter; Wenting Lin; Wenyu Li; Chong Peng; Wei Li (Chemical Engineering Journal, 2026)

Scale-Up performance and high-cell-density operation of a three-stage PHA biorefinery using liquor-making wastewater - Qingxin Liu; Menghan Wu; Yandong Xie; Jiayu Liu; Mengsha Mu; Peng Yu; Hui Wang (Water Research, 2026)

Sulforaphane attenuates oxidative stress and vascular remodeling in indium lung disease rats via mediating the NF-κB and Nrf2 pathways - Peng Wan; Fuyuan Cao; Gai Li; Xiaohui Hao; Yu Mu; Jian Sun; Ling Xue; Nan Liu (Toxicology and Applied Pharmacology, 2026)

Combined exposure to flumethrin and hexaconazole induces synergistic oxidative, metabolic, and immune dysregulation in honeybees - Tao Cang; Ying Wang; Xinfang Li; Xin Peng; Qihe Zhao; Xiyan Mu; Guojun Zhou; Yanhua Wang (Journal of Hazardous Materials, 2026)

A physics-guided and scene-adaptive water index for consistent surface water mapping across regions and seasons - Shanchuan Guo; Pengfei Tang; Zilong Xia; Haowei Mu; Xiaoquan Pan; Peng Zhang; Yu Chen; Peijun Du (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Tuning oxygen vacancy density via facet engineering of TiO2 for selective photocatalytic hydrogenation of 5-hydroxymethylfurfural - Yunlei Zhang; Chaoyue Xu; Xiaotong Mu; Hongke Li; Jian Cao; Maobin Wei; Peng Wang; Yao Chen (Fuel, 2026)

Insights into the molecular basis of umami in premium green teas via integrated metabolomics, peptidomics, and in silico molecular docking - Jiaqi Yang; Shitao Fang; Qi Zhou; Yizhi Wang; Kangni Yan; Peng Qunhua; Lin Zhi; Wu Yan; Fu Jianyu; Mu Dan; Lv Haipeng; Shi Jiang (Food Chemistry, 2026)

Cl−-repelling Mn3O4/Co(OH)2 heterojunction on self-supporting N-doped CNTs for high-stability seawater zinc-air batteries - Lin Mu; Yuxin Yao; Haibo Zhao; Shifang Yang; Ying Wang; Peng Yu (Chemical Engineering Journal, 2026)

Self-assembly-confined upconversion photogelation enables centimeter-deep curing for rapid deep-organ hemostasis with sustained pain modulation - Qian Chen; Hongyu Wen; Peng Zhang; Xuhui Xu; Hanying Wang; Guizhu Feng; Qiqi Pei; Li Tian; Yuanyuan Cao; Hongwei Qin; Fusheng Luo; Zhaowei Teng; et al. (Chemical Engineering Journal, 2026)

Photothermal-amplified single-atom platinum nanozymes on black phosphorus for deep antibacterial therapy - Bairui Zeng; Dongyang Zheng; Anni Wu; Yanjing Zhang; Peng Ding; Zhixiang Mu; Junhao Xiang; Shuangshuang Xu; Xiaoliang Qi; Jianliang Shen; Zhennan Deng (Chemical Engineering Journal, 2026)

Laser-processed biomimetic hydrogel patches with tunable bio-adhesion, muscle tissue regeneration, and synergistic antibacterial activity - Luxing Wei; Jun Huang; Yingwen Mu; Liuguang Song; Yi Yu; Yuquan Wang; Gexing Peng; Ningji Gong; Jian Shen (Chemical Engineering Journal, 2026)

Differential driving mechanisms on saline-alkali land in desert and oasis of arid and semi-arid regions - Lei Zhang; Xia Jia; Yonghua Zhao; Manya Luo; Qi Mu; Peng Zhang; Yu Bai (CATENA, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Collaborative Optimization of Capacity and Operation Strategy for an Air-Source and Ground-Source Heat Pump Coupled Heating System - Huan Liu; Junqing Liu; Peng Li; Yanru Lu; Xiaojie Niu; Jinghui Luo; Yongchao Mu (Applied Geophysics, 2026)

Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

A new strategy to reduce casein antigenicity: Investigating immune response, gut microbiota dysbiosis, and metabolic changes in allergic mice - Qi Sun; Peng Sun; Qing Zhao; Xiaomeng Wu; Fanhua Kong; Guangqing Mu (Food Chemistry, 2026)

Decoding novel umami peptides from soy protein isolate hydrolysate: Mechanistic insights via multisensory techniques, machine learning and molecular docking - Xueying Song; Dipeng Mei; Yihan Mu; Peng Cheng; Siliang Wu; Chenchen Cao; Guowan Su (Food Bioscience, 2026)

MPM analysis of wetting-induced failure in collapsible loess slopes - Z.Q. Zhan; C. Zhou; Q.Y. Mu; Z. Gong; J.B. Peng (Computers and Geotechnics, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Development and application of KASP molecular marker for accelerated breeding of low-acid Cerasus humilis cultivars - Xia-Yu Xing; Xiao-Yan Wang; Yue-Zhan Xiao; Hao-Nan Wang; Hou-Qiang Song; Ming Liu; Xiao-Peng Mu; Jian-Cheng Zhang; Lu-Ting Jia; Yu Gary Gao; Shuai Zhang; Peng-Fei Wang (Plant Cell Reports, 2026)

Substantial discrepancies across global fire emissions inventories: a systematic intercomparison - Jiyuan Yang; Hanyue Zheng; Peng Zhao; Johannes W. Kaiser; Qing Mu (Journal of Environmental Sciences, 2026)

Underestimated small thermokarst lakes of the Qinghai-Tibet Plateau and their carbon emission potential - Xiaoqing Peng; Hengxing Luo; Weiwei Tian; Zhuoxuan Xia; Oliver W. Frauenfeld; Cuicui Mu; Lin Liu; Jing Luo; Lingcao Huang; Qinshan Zhao; Yimiao Yin (Global and Planetary Change, 2026)

Sustainable stabilisation of collapsible loess with quicklime-recycled GGBS mixtures - Bao-Lin Dai; Chao Zhou; Qing-Yi Mu; Jian-Bing Peng (Geomechanics for Energy and the Environment, 2026)

Enabling long-cycle-life high-voltage calcium metal batteries with fluorinated alkoxyborate-based CaNa hybrid electrolytes - Xinyue Li; Shuangshuang Cui; Bin Chen; Xiaoke Mu; Dechen Zeng; Hongkun Wang; Yang Wang; Bo Peng; Tianyu Zheng; Dianxing Ju; Aobing Du; Zhenyou Li; et al. (Chemical Engineering Journal, 2026)

Soil infiltration responses to vegetation restoration along a precipitation gradient on the loess plateau - Shuyu Zhang; Guangju Zhao; Yuanhao Liu; Peng Tian; Xingmin Mu (CATENA, 2026)

Coupled influence of Western Pacific moisture anomalies and mid-tropospheric humidity on October precipitation in Yunnan Province Southwest China - Wen-Jun Sun; Zhen-Peng Tao; Zi-Yang Zhang; Tian-Qing Lan; Taohui Li; Peng Zi; Jian Zhang; Yao Wu; Ming-Qiang Liang; Chao-Jun Chen; Yuan-Yuan Mu; Jun-Yun Li; et al. (Atmospheric Research, 2026)

Hyoscyamine Ameliorates Repetitive Behavior in NLG1 and SHANK3 Deficient-Mice - Dandan Lv; Ruining Liu; Xinyu Zhang; Siqi Peng; Wei Xie; Mingdao Mu; An Liu (Neuroscience Bulletin, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Disentangling the mechanisms shaping the biogeographic patterns of bacterial and archaeal communities in rural drinking water sources of North and East China - Xuekai Dou; Xiaoying Mu; Shier Huang; Weixiao Qi; Xiaofeng Cao; Jianfeng Peng; Huijuan Liu (Process Safety and Environmental Protection, 2026)

Volatile organic compounds from Meyerozyma guilliermondii JY19 trigger apoptosis-like cell death in Botrytis cinerea and control postharvest gray mold of ginseng berries - Guanzhong Ding; Fan Zhou; Peng Mu; Lidan Zhang; Yue Zhang; Yidong Zheng; Wenwen Jiang; Ning Liu (Postharvest Biology and Technology, 2026)

Preferential flow reduces overland flow on slopes: insights from a field experiment on the Chinese Loess Plateau - Yongfu Wen; Chaojun Gu; Peng Gao; Jiahui Zhou; Xiaoxue Guo; Xingmin Mu; Xucheng Ai; Ruidun Zhang; Siyu Ren (Journal of Hydrology, 2026)

Evaluating the performance of coastal virtual stations from different combinations of altimetry missions - Fukai Peng; Zhong He; Xiaoli Deng; Ole Baltazar Andersen; Dapeng Mu; Yunzhong Shen; Yanguang Fu; Xiao Cheng (Advances in Space Research, 2026)

Bayesian-Optimized Neural Networks with High-Fidelity FEM for Intelligent Residual Strength Prediction in Damaged Ships - Jianxiao Deng; Fei Peng; Jinlei Mu; Hailiang Hou (Journal of Marine Science and Engineering, 2026)
The rapid and accurate assessment of residual ultimate strength after ship damage is crucial for rescue decision-making and navigation safety, while traditional methods struggle to meet the demands of complex random damage scenarios in terms of efficiency or accuracy. This study proposes a hybrid framework that integrates high-fidelity nonlinear finite element simulation (NFEM) and a Bayesian-regularized backpropagation neural network (BPNN). NFEM is used to accurately simulate a large number of random damage scenarios, generating a physically credible benchmark dataset. BPNN serves as an efficient surrogate prediction model, with its key parameters—the number of hidden layers and the training algorithm—systematically optimized to enhance generalization capability. The results show that: (1) The NFEM simulation results deviate by less than 5% compared to the Smith method, validating the reliability of the dataset. (2) The prediction performance of BPNN is highly dependent on the number of hidden layers and the training algorithm, exhibiting non-monotonic variation, with an optimal parameter combination identified as 8 hidden layers paired with the Bayesian algorithm, achieving a prediction regression value R of 0.91662. (3) Deep networks are prone to overfitting, while shallow networks suffer from insufficient feature capture. (4) The Bayesian algorithm performs best in terms of overfitting resistance and stability. This study not only provides a high-precision and efficient intelligent solution for residual strength assessment of damaged hulls, but its systematic neural network parameter optimization strategy, particularly the approach of identifying optimal depth and selecting anti-overfitting algorithms, also offers an important reference for the design of intelligent damage assessment models for similar engineering structures.

Combined transcriptome and metabolome analyses reveal that galactose metabolism is vital for tobacco in response to low-nitrate stress - Dong Wang; Yongchang Wen; Haoran Xie; Mingxin Mu; Xianchao Peng; Junju Li; Jixian He; Xiaoli Liu; Yifei Lu; Bi Ren; Liming Lu; Liqin Li (Journal of Genetics, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

CoTiO3 immobilized on nickel foam for degradation of levofloxacin via peroxymonosulfate activation: Electron transfer pathways and degradation mechanism - Zhonghua Mu; Peng Cui; Rui Gao; Jikai Liu; Wei Li; Yushu Zhang; Wenqiang Ma; Hairui Li; Shiqi Wu; Shuzheng Zhang; Zhaohui Wang; Lei Yang; et al. (Process Safety and Environmental Protection, 2026)

Global Fixed-Time Path-Following Control with Prescribed Performance for an Unmanned Surface Vehicle under Lumped Uncertainties and Input Saturation: Simulations and Experiments - Baojian Song; Yunsheng Fan; Dongdong Mu; Guofeng Wang; Peng Liu; Yaxuan Wang (Ocean Engineering, 2026)

Seawater pH fluctuations during the Ordovician to Silurian transition: Insights from δ11B records in carbonates - Xiangrong Yang; Shaojie Li; Detian Yan; Yue Cai; Denglin Han; Ke Xu; Yanqing Li; Can Chen; Peng Sun; Mu Liu; Chunyao Liu; Daizhao Chen (Global and Planetary Change, 2026)

Sustainable and selective gold extraction from electronic waste using conjugated microporous polymer aerogels - Wei Liu; Zhaoqi Zhu; Xicheng Liu; Mengqi Zhao; Rui Jiao; Peng Mu; Hanxue Sun; An Li (Chemical Engineering Journal, 2026)

Distinct and interactive effects of multiple consumers on plant trade‐offs and diversity in alpine meadows - Yimin Zhao; Peng Zhang; Junsheng Ke; Yilin Dang; Kui Hu; Zijian Yu; Hongying Jiang; Chenrui Wang; Wenjie Li; Jing Zhang; Dong Zhang; Xue Zhang; et al. (Ecology, 2026)
Plants face a fundamental trade‐off between acquiring resources for growth or interspecific competition and simultaneously investing in anti‐consumer defenses. These selective pressures shape species' life history strategies and promote stable coexistence. However, the specific roles of distinct consumer groups, particularly the often‐overlooked oomycetes, in driving growth–defense trade‐offs and sustaining plant diversity remain poorly understood. To this end, we conducted a factorial field experiment in an alpine meadow on the Qinghai‐Tibetan Plateau, manipulating the nitrogen supply (to test resource acquisition effects) and removing consumer groups (i.e., mammalian herbivores, fungi, and oomycetes) both individually and in combination. We used standardized major axis regression to investigate how plant species differentially allocate resources between growth, competition, and defense, and how such trade‐offs influence plant species diversity. Species' responses to nitrogen addition and consumer removal were positively correlated, supporting the existence of widespread growth–defense trade‐offs. The strength of this trade‐off varied significantly among consumer removal treatments, with fungi and herbivores exerting stronger effects than oomycetes. The removal of both herbivores and oomycetes amplified their individual impacts on plant growth–defense trade‐offs. Consistent with this pattern, the removal of fungi or herbivores, but not oomycetes, led to pronounced declines in plant diversity. Our findings reveal the divergent roles of individual consumer groups in shaping plant life history strategies and highlight that cross‐trophic interactions, particularly those involving herbivores or fungal pathogens, are critical for maintaining plant diversity.

Trace carbonyls in water reuse: Structure-dependent multi-barrier penetration and enhanced deep mineralization via dual-radical oxidation synergism - Yun-Peng Wu; Qian-Yuan Wu; Zi-Bo Jing; Yu-Ming Tian; Jiang-Lei Xiong; Mu-Da Han; Sheng-Mei Li; Er-Dong Wang; Wen-Long Wang (Water Research, 2026)

Finite-time adaptive event-triggered control for USV trajectory tracking combined with intrinsic curiosity sequential proximal policy optimization - Xiaoning Zhang; Yunsheng Fan; Shengli Dong; Zhipeng Shen; Dongdong Mu; Xiang Ye; Peng Liu (Ocean Engineering, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Corrigendum to “Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus” [Fish Shellfish Immunol. 165 (2025) 110566] - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2026)

Response of soil conservation functions to vegetation dynamics and restoration potential on the Loess Plateau - Xiaoxue Guo; Peng Tian; Guangju Zhao; Peng Gao; Chaohui Ma; Rui Shan; Jiahui Zhou; Xingmin Mu (CATENA, 2026)

Development and application of a distributed hydrology and soil erosion model in a semi-arid catchment, China - Ang Lu; Peng Tian; Guangju Zhao; Xingmin Mu; Xiaojing Tian; Chaojun Gu; Lin Yang; Junjian Fan (CATENA, 2026)

Decoupling effects of driving factors on sediment load in the middle reaches of the Yellow River - Chaohui Ma; Xiaoxue Guo; Ruirui Xu; Peng Gao; Jiahui Zhou; Yuxuan Zhang; Xingmin Mu (CATENA, 2026)

MetaSD: a unified framework for scalable downscaling of meteorological variables in diverse situations - Jing Hu; Honghu Zhang; Peng Zheng; Jialing Mu; Xi Wu; Xiaomeng Huang (Climate Dynamics, 2026)

Lithological controls on SOC fractions through the coupling of microbial CAZyme genes and necromass in karst and non-karst forests - Tao Yang; Mu Yang; Jinxing Zhou; Xiawei Peng (Applied Soil Ecology, 2026)

Liver-specific SLC13A3 modulation alleviates MASLD by regulating NAD+ metabolism - Jiangxia Du; Minhui Shen; Yuan Mu; Shuoran Peng; Zhifei Xu; Xiaochun Yang; Bo Yang; Peihua Luo; Hao Yan; Qiaojun He (Molecular and Cellular Biochemistry, 2026)

Effects of high-pH saline-alkaline water on tissue structure, osmoregulation, antioxidant capacity, and metabolic activity in mud crab Scylla paramamosain Estampador, 1950 - Yuntao Li; Cunhong Chen; Zihui Li; Jingli Yang; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; et al. (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Emerging catalysts for catalytic ozone advanced oxidation in water purification: Metal-organic frameworks and their derivatives - Tianle Li; Zhichong Mu; Chaohai Wang; Jinhui Zhang; Rongfu Peng; Junning Wang; Yanli Mao; Xinfeng Zhu (Environmental Research, 2026)

Tracing sediment sources during rainfall events in a northern Loess Plateau catchment using geochemical and mid-infrared spectral methods - Rui Shan; Peng Tian; Ang Lu; Xiaoxue Guo; Xingmin Mu; Haoyu Zhu; Geng Ren; Guangju Zhao (Journal of Mountain Science, 2026)

Transboundary dispersion and deposition of gaseous radioactive iodine revealed by anthropogenic 129I in mountainous regions - Yanyun Wang; Jie Zhou; Mu Lin; Yukun Fan; Peng Cheng; Luyuan Zhang; Huan Jiang; Ning Chen; Qi Liu; Ge Xu; Xiaolin Hou (Journal of Hazardous Materials, 2026)

Hypoxanthine accumulation caused by mutations of Bombyx mori xanthine dehydrogenase triggers female sterility - Wen-qing Lai; Zhan-peng Lu; Qiang Zhang; Zuo-min Shao; Han Gao; Xia Sun; Sheng Qin; Xue-yang Wang; Mu-wang Li (Insect Biochemistry and Molecular Biology, 2026)

Characterization of monoclonal antibody against IgM and phagocytic function of IgM+ B cells in snakehead (Channa argus) - Peng Fei Mu; Zhe Wang; Qi Li; Qiu Hua Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Flexible dual-mode capacitive sensor based on snowflake-like flowable electrode and multi-level microstructured dielectric layer with long proximity sensing distance and high linear sensitivity - Yuxia Li; Wenzheng Song; Liangsong Huang; Peng Zhang; Liqun Yang; Zhichao Mu; Ranran Yang; Yuteng Tang (Chemical Engineering Journal, 2026)

Etched MOF-reinforced nanocellulose aerogels with hierarchical porosity for synergistic flame retardancy, thermal insulation, and self-cleaning - Jing Ren; Junfeng Peng; Mengmeng Guo; Jing Li; Zimeng Mu; Chunzu Cheng; Min Gao; Qun Li; Zhiqiang Li (Chemical Engineering Journal, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Revealing dissolution process and mechanism of montmorillonite by two stereoisomers of malic acids and its effect on the Cr(III) retention properties: Insights from DFT simulations and experimental studies - Jingjie Yang; Li Zeng; Yong Wang; Song Liu; Aiqin Wang; Liang Bian; Temirlan Arslanov; Bin Mu; Hailiang Dong; Peng Liu; Xiaobin Gu (Chemical Engineering Journal, 2026)

Vegetation zonation across elevational gradients considering lithological influence: A case study from the Qinling Mountains heartland, China - Bailei Shi; Yanjun Shen; Jianbing Peng; Qingyi Mu; Bingquan Wu; Jinyu Zhu; Shengwei Zhang (CATENA, 2026)

Comprehensive assessment of secondary metabolite diversity and in vitro anti-diabetic properties in Sanghuangporus quercicola cultured under different conditions - Mingxing Yu; Na Zhang; Xiaofeng Ma; Xiaoshuang Zhou; Shude Yang; Weihang Peng; Yin Li; Yuejun Mu; Xianhao Cheng; Rui Zhang; Yongfei Ming (Systems Microbiology and Biomanufacturing, 2026)

Acute effects of two different combined exercise modalities on executive function and circulating neurotrophic factors in young healthy adults - Yi-Hung Liao; Toby Mündel; Ying-Chu Chen; Shiow-Chwen Tsai; Kuo-Cheng Wu; Mu-Tsung Chen; Li-Chen Lee; Chih-Peng Su; Yu-Kai Chang; Chung-Yu Chen (European Journal of Applied Physiology, 2026)

APPLE-GO: Modeling high-spatial resolution forest canopy reflectance with effect of Adjacent Pixels using Path Length Extended Geometric Optical theory - Qunchao He; Siqi Yang; Naijie Peng; Wenjie Fan; Xihan Mu; Biao Cao; Dechao Zhai; Zhicheng Huang; Huazhong Ren; Guangjian Yan (Remote Sensing of Environment, 2025)

The predictability study of oceanic deep learning models: Taking Kuroshio intrusion into South China Sea as an example - Qiang Wang; Junkai Qian; Mu Mu; Peng Liang; Bo Qin (Ocean Modelling, 2025)

Refined evaluation of winter wheat drought and climate change implications - Junfang Zhao; Huiwen Peng; Yunkun Song; Jiaxin Wang; Jia Mu (Journal of Cleaner Production, 2025)

Discontinuation of glacial meltwater input reshapes the diversity and stability of eukaryotic planktonic microbial communities in glacial lakes - Xiaodong Li; Qianggong Zhang; Peng Zhang; Qing Yang; Zijian Lu; Yanan Zhou; Meiqi Huang; Guangli Mu; Zhao Xue; Linyuan Lu; Yindong Tong (Environmental Research, 2025)

Morphology of root systems and tensile properties of individual roots across various soil types and layer thicknesses induced by bedrock weathering - Bin-bin Guo; Qing-yi Mu; Yan-jun Shen; Anthony Kwan Leung; Jian-bing Peng (CATENA, 2025)

Transitions in slope runoff generation mechanisms induced by land use change in the Loess Plateau, China - Jiahui Zhou; Yongfu Wen; Peng Gao; Siyu Ren; Xiaoxue Guo; Xingmin Mu (CATENA, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

Anti-melanogenic effect and mechanism of oxypaeoniflorin derived from edible Paeonia ostii flower on melanogenesis in B16F10 cells and zebrafish - Kejie Peng; Yixuan Wang; Zhangtie Wang; Jing Wang; Yuhang Zhu; Qiannan Pan; Yumeng Li; Jian Mu; Xiuxin Zhang; Baiyi Lu (Food Bioscience, 2025)

Application of a machine learning-based food risk framework to assess the public dietary risk of cadmium in China - Peng Deng; Xiangang Hu; Li Mu; Fubo Yu; Linyue Luo (Environmental Pollution, 2025)

A unified understanding and calculation method of the compression behavior of loess with different particle size distributions and sample preparation methods across the Chinese Loess Plateau - Zhiyuan He; Qingyi Mu; Penghui Ma; Zhijie Jia; Jianbing Peng (Computers and Geotechnics, 2025)

Mechanistic insights into enhanced volatile pyridine biodegradation through shortcut pyridine-N transformation in counter-diffusion biofilms by regulating biofilm stratification and microbial spatial interactions - Peng Zheng; Yan Li; Youpeng Cheng; Jing Wang; Yixuan Wang; Yang Mu; Jinyou Shen (Bioresource Technology, 2025)

Synergistic Enhancement of Plant Drought Tolerance by PYL and ABA—A Review - Rongrong Zhang; Shilei Luo; Long Li; Tingting Mu; Peng Wang; Guobin Zhang (Journal of Plant Growth Regulation, 2025)

Dysfunction of cerebrospinal fluid circulation and neurovascular decoupling in end-stage renal disease patients with mild cognitive impairment - Zhaoyao Luo; Lurui Bo; Xinyi Zhu; Qiange Zhu; Huijie Yuan; Wen Gu; Peng Li; Yihao Peng; Xiang Chen; Ming Zhang; Shaohui Ma; Junya Mu (GeroScience, 2025)
End-stage renal disease (ESRD) patients frequently experience mild cognitive impairment (MCI), which significantly affects their quality of life. Although dysfunctions in cerebrospinal fluid (CSF) circulation and neurovascular coupling (NVC) have been implicated in cognitive impairment, their interrelationship remains unclear. This study aimed to investigate the association between CSF circulation dysfunction and NVC disruption in ESRD patients with MCI. We enrolled 68 ESRD patients with MCI and 65 healthy controls (HCs). CSF circulation was assessed using choroid plexus volume (CPV), the diffusion tensor imaging along the perivascular space (DTI-ALPS) index, and perivascular space volume fraction (PVSVF). NVC was evaluated using coupling metrics between cerebral blood flow (CBF) and resting-state functional magnetic resonance imaging (MRI) indicators: amplitude of low-frequency fluctuation (ALFF), fractional ALFF (fALFF), and regional homogeneity (ReHo). Cognitive performance was measured using a battery of neuropsychological tests. Compared to HCs, ESRD patients showed significantly increased CPV ( P < 0.001) and enlarged PVSVF ( P < 0.05), along with a decreased DTI-ALPS index ( P < 0.01). Global and regional NVC metrics were significantly reduced in ESRD patients ( P < 0.001). Moreover, regional NVC metrics were negatively correlated with CPV. Mediation analysis further revealed that CBF-ReHo coupling in the left cingulate gyrus pregenual area 32 mediated the relationship between elevated LCPV and cognitive decline. These findings suggest that CSF circulation dysfunction and impaired NVC are interrelated in ESRD-MCI. Disruption of CSF circulation may contribute to cognitive decline by impairing NVC, highlighting both as potential targets for early diagnosis and intervention in ESRD-related cognitive impairment.

Soil physicochemical properties and roots promoted preferential flow development after vegetation restoration - Yongfu Wen; Mengzhen Li; Peng Gao; Jiahui Zhou; Xucheng Ai; Yuxuan Zhang; Xingmin Mu (Journal of Hydrology, 2025)

Skeleton engineering of conjugated microporous polymer for highly efficient PM capture in harsh environments - Cailin Guo; Wei Liu; Mengxue Li; Peng Mu; Anli Yi; Zhaoqi Zhu; Rui Jiao; Hanxue Sun; An Li (Journal of Hazardous Materials, 2025)

Integrated machine learning model for prediction of nutrients contents and maturity in rural organic solid wastes aerobic composting - Hao Peng; Lan Mu; Yingjin Song; Hong Su; Yadong Ge; Zhanjun Cheng; Rundong Li; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Identification and functional characterization of cGAS and cGAS-like in snakehead Channa argus - Hong Qing Zhang; Long Wei Cai; Yu Hang Deng; Meng Xin Yan; Peng Fei Mu; Bo Li; Lan Hao Liu; P. Nie (Fish & Shellfish Immunology, 2025)

Water retention curves of a deformable lean clay under various stress ratios: Emphasizing the pore shape effects - Qing-yi Mu; Tian-qi Song; Chao Zhou; Jian-bing Peng (Computers and Geotechnics, 2025)

The vital role of current-topography interaction and tidal mixing in the upwelling around Zhoushan Archipelago - Jianshe Mu; Juncheng Xie; Peng Bai; Bo Li; Jingling Yang; Ying Gao (Continental Shelf Research, 2025)

Lymph node-targeted delivery of cancer vaccine with natural plant derivatives potentiates antitumor efficacy through improved antigen presentation - Jiankang Mu; Zhonglian Wei; Ziyi Chen; Ping Wang; Haoran Wang; Peng Cao (Chemical Engineering Journal, 2025)

Water and sediment yield in the source region of the Yellow River, northeastern Tibetan Plateau: Historical pattern, future evolution, and attribution analysis - Ruirui Xu; Dexun Qiu; Peng Gao; Xingmin Mu (CATENA, 2025)

Unlocking the synergistic effects in biomass-plastic Co-pyrolysis using a hybrid machine learning approach with blended rule descriptors - Peng Jiang; Wenjie She; Hao Zhang; Lin Li; Han Lin; Tuo Ji; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Biomass and Bioenergy, 2025)

Multi-constraint analysis reveals distinct aerosol effects on high cloud properties at SACOL and SGP sites - Yang Xia; Jinming Ge; Qingyu Mu; Yue Hu; Nan Peng; Ziyang Qin; Xiang Li; Chi Zhang; Bochun Liu (Atmospheric Research, 2025)

Dynamic role of selenium in soil–plant-microbe systems: Mechanisms, biofortification, and environmental remediation - Guangai Deng; Zhiquan Fan; Zhiyong Wang; Mu Peng (Plant and Soil, 2025)

Tissue-Selective Separation Mechanism of Multi-type Soft Tissues Under Waterjet Impact for Low-Trauma Cutting Surgery - Jiaqi Zhao; Xiao-Fei Song; Xiaoxian Wei; Jiuke Mu; Peng Peng; Wenli Yu (Annals of Biomedical Engineering, 2025)

Deformable USV and Lightweight ROV Collaboration for Underwater Object Detection in Complex Harbor Environments: From Acoustic Survey to Optical Verification - Yonghang Li; Mingming Wen; Peng Wan; Zelin Mu; Dongqiang Wu; Jiale Chen; Haoyi Zhou; Shi Zhang; Huiqiang Yao (Journal of Marine Science and Engineering, 2025)
As crucial transportation hubs and economic nodes, the underwater security and infrastructure maintenance of harbors are of paramount importance. Harbors are characterized by high vessel traffic and complex underwater environments, where traditional underwater inspection methods, such as diver operations, face challenges of low efficiency, high risk, and limited operational range. This paper introduces a collaborative survey and disposal system that integrates a deformable unmanned surface vehicle (USV) with a lightweight remotely operated vehicle (ROV). The USV is equipped with a side-scan sonar (SSS) and a multibeam echo sounder (MBES), enabling rapid, large-area searches and seabed topographic mapping. The ROV, equipped with an optical camera system, forward-looking sonar (FLS), and a manipulator, is tasked with conducting close-range, detailed observations to confirm and dispose of abnormal objects identified by the USV. Field trials were conducted at an island harbor in the South China Sea, where simulated underwater objects, including an iron drum, a plastic drum, and a rubber tire, were deployed. The results demonstrate that the USV-ROV collaborative system effectively meets the demands for underwater environmental measurement, object localization, identification, and disposal in complex harbor environments. The USV acquired high-resolution (0.5 m × 0.5 m) three-dimensional topographic data of the harbor, effectively revealing its topographical features. The SSS accurately localized and preliminarily identified all deployed simulated objects, revealing their acoustic characteristics. Repeated surveys revealed a maximum positioning deviation of 2.2 m. The lightweight ROV confirmed the status and location of the simulated objects using an optical camera and an underwater positioning system, with a maximum deviation of 3.2 m when compared to the SSS locations. The study highlights the limitations of using either vehicle alone. The USV survey could not precisely confirm the attributes of the objects, whereas a full-area search of 0.36 km2 by the ROV alone would take approximately 20 h. In contrast, the USV-ROV collaborative model reduced the total time to detect all objects to 9 h, improving efficiency by 55%. This research offers an efficient, reliable, and economical practical solution for applications such as underwater security, topographic mapping, infrastructure inspection, and channel dredging in harbor environments.

Epithelial cells facilitate tissue fibrosis through early growth response-1 overexpression in IgG4-related disease - Ruijie Sun; Qinhuan Luo; Mu Wang; Linyi Peng; Wei Wei; Yanmei Li; Jiaxin Zhou; Yuxue Nie; Jingna Li; Qing Zhong; Yunyun Fei; Mengtao Li; et al. (Science Bulletin, 2025)

A rapid bag-protected micro-solid-phase extraction of polychlorinated biphenyls based on dual-ligand hollow MOF: one-stone-three-birds strategy from KMnO4 - Xuemei Wang; Jiyun Chen; Jie Zhang; Fu Mu; Zhen Zhang; Rao Peng; Xinzhen Du; Xiaoquan Lu (Chemical Engineering Journal, 2025)

Comparative analysis of rural organic waste treatment: greenhouse gas emissions, economics, and energy flow - Hao Peng; Lan Mu; Yingjin Song; Dan Zeng; Hong Su; Zhanjun Cheng; Rundong Li; Guanyi Chen (Biomass and Bioenergy, 2025)

Failure mechanism of a loess-red silty clay interface landslide on the Heifangtai platform, China - Penghui Ma; Zekun Li; Jianqi Zhuang; Qingyi Mu; Jiaxu Kong; Jianbing Peng (Bulletin of Engineering Geology and the Environment, 2025)

Bone marrow microenvironment-targeted yolk-shell nanoparticle enhances acute myeloid leukemia chemotherapy by preventing endothelial cell/ECM-mediated adhesion - Shiyi Hong; Pei Peng; Yutian Huang; Siying Cai; Cao Yao; Tongtong Huang; Yulu Ying; Wei Li; Yang Xiong; Mancang Gu; Guilin Cheng; Chaofeng Mu (Chemical Engineering Journal, 2025)

Characteristics and environmental significance of sulfur isotope signatures in the water environment of typical pyrite mines - Weiqing Zhou; Peng Liu; Jianwei Zhou; Junxing Liu; Chunguang Wang; Haowei Mu; Han Jia; Jinxing Zuo (Journal of Environmental Sciences, 2025)

The effects of the 2D aligned fibers on the fracture properties of steel fiber reinforced cementitious composite slab: Simulation and experimental validation - Kelai Yu; Yu Hu; Ru Mu; Peng Xing; Nan Zhao; Longbang Qing (Engineering Structures, 2025)

Long time-series change characteristics and suitable scale of oasis in arid and semi-arid regions of China - Lei Zhang; Xia Jia; Yonghua Zhao; Manya Luo; Qi Mu; Hongliang Kang; Peng Zhang (Applied Geography, 2025)

Development of cell labeling and gene editing tools in urochordate Ciona - Xiang Li; Lu Mu; Hongzhe Peng; Sun Nyunt Wai; Longjun Pu; Bo Dong (Marine Life Science & Technology, 2025)
Urochordate Ciona spp. are ideal marine model organisms for studying embryogenesis and developmental and evolutionary biology. However, the effective implementation of genetic labeling and CRISPR/Cas9-based editing tools at cellular resolution remains challenging. This study successfully developed and validated a collection of Gateway-based vectors for cell labeling in Ciona spp. The destination vector sets contained two Gateway cassettes flanked by Minos sites, allowing the N- or C-terminal tagging of a protein of interest with various fluorescent markers. In addition, we optimized the CRISPR/Cas9 and CRISPR/dCas9 systems by incorporating P2A-mCherry, a fluorescent indicator for Cas9 expression at cellular resolution. We demonstrated the effective destruction or inhibition of target genes when CRISPR constructs were introduced into fertilized eggs. Furthermore, we engineered a dual fluorescence sensor system that helps visualize successful gene knockouts at the cellular level in specific tissues. The genetic tools developed in this study offer a robust method for gene expression, cell tracking, and subcellular protein localization while also facilitating tissue-specific functional analysis in Ciona embryos and other model systems.

Mechanistic insights into substituent-induced hydrolytic debromination and electron flow of bromophenols under nitrate-reducing conditions - Yunhao Xu; Jing Wang; Qiang Chi; Peng Zheng; Hanjuan Lv; Yang Mu; Jinyou Shen (Journal of Hazardous Materials, 2025)

Isolation, identification, and virulence of three strains of Beauveria bassiana from silkworms, Bombyx mori - Qiang Zhang; Wenqing Lai; Qin Li; Xiaoying Zhang; Zhan-peng Lu; Jiawei Jiang; Wenjing Yu; Zuo-min Shao; Xue-yang Wang; Mu-wang Li (Journal of Asia-Pacific Entomology, 2025)

Significant effects of earthworm species on antibiotic resistome in livestock manure as revealed by metagenomic analysis - Ming Yang; Liang Peng; Meirui Mu; Fengxia Yang; Zhonghan Li; Bingjun Han; Keqiang Zhang (Environmental Pollution, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Maintaining shallow waters to maximize the potential of saltpans as foraging habitat for migratory shorebirds along an endangered flyway - Weipan Lei; José A. Masero; Ziwen Chai; Bing-Run Zhu; Tong Mu; He-Bo Peng; Zhengwang Zhang; Theunis Piersma (Biological Conservation, 2025)

Silicon Promotes Na+ Compartmentalization and Mineral Uptake in Zucchini Seedlings to Maintain Physiological Homeostasis and Alleviate Salt Stress - Rongrong Zhang; Guoshuai Wang; Shilei Luo; Long Li; Tingting Mu; Peng Wang; Guobin Zhang (Journal of Plant Growth Regulation, 2025)

Hydrothermal drivers of seasonal and interannual dynamics of soil respiration and its temperature sensitivity in a temperate semiarid shrubland - Shengjie Gao; Xin Jia; Xiaoyan Jiang; Yanmei Mu; Charles P.-A. Bourque; Peng Liu; Shugao Qin; Yun Tian; Wenjing Chen; Tianshan Zha (Agricultural and Forest Meteorology, 2025)

Mild cognitive impairment is associated with effect of uremic metabolites on gray matter structural changes in end-stage kidney disease - Huijie Yuan; Zhaoyao Luo; Jing Yang; Shaohui Ma; Peng Li; Xinyi Wang; Hang Su; Ronghua He; Junya Mu; Yuchen Zhang (Brain Imaging and Behavior, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Smart temperature sensors based on flexible CB/TPU/ PVDF membranes for eliminating pressure interference - Shuo Li; Jiaxin Sun; Feng Tong; Guo Chen; Zhefu Mu; Xiaoqiang Zhang; Sheng Huang; Zheng Chen; Lei Xu; Changyun Li; Peng Wang; Xiuquan Gu (Chemical Engineering Journal, 2025)

Nanocomposite hydrogel with multiple metal ions coupling for effective treatment of bacteria infected wound via cascade catalysis and tissue regeneration - Yating Liu; Wenyun Mu; Yu Wang; Tao Liu; Zhenzhen Peng; Xin Chen (Chemical Engineering Journal, 2025)

When crop straw meets CO2-intensive process industries in China: The potential of CO2 mitigation and techno-economic analysis - Minjiao Chen; Peng Jiang; Meihua Li; Guanhan Zhao; Han Lin; Liwen Mu; Lee Chung Lau; Jiahua Zhu (Biomass and Bioenergy, 2025)

Oxidative Stress-mediated Loss of Hippocampal Parvalbumin Interneurons Contributes to Memory Precision Decline After Acute Sleep Deprivation - Yu-zhu Gao; Kai Liu; Xin-miao Wu; Cui-na Shi; Qiu-li He; Hai-peng Wu; Jian-jun Yang; Hao Yao; Mu-huo Ji (Molecular Neurobiology, 2025)

Effect of on stereoisomers of lactic acids on microbially-mediated reductive dissolution of clay minerals: Insights from DFT and experimental studies - Jingjie Yang; Liang Bian; Aiqin Wang; Xiaofeng Zhao; Jianan Nie; Temirlan Arslanov; Bin Mu; Hailiang Dong; Mianxin Song; Li Zeng; Peng Liu; Xiaobin Gu (Applied Clay Science, 2025)

Dietary supplementation with Pediococcus pentosaceus promotes resistance to betanodavirus and ranavirus in giant groupers - Chun-Kuei Chang; Zhe-Li Lin; Yu-Hsuan Kai; Mu-Yun Peng; Yu-Chi Wu (Aquaculture, 2025)

A review of the interaction mechanisms between jasmonic acid (JA) and various plant hormones, as well as the core regulatory role of MYC2 - Tingting Mu; Shilei Luo; Long Li; Rongrong Zhang; Peng Wang; Guobin Zhang (Plant Science, 2025)

Genesis, characteristic and disaster effects of loess meso-interfaces: A field geological investigation - Luqing Zhao; Penghui Ma; Jianbing Peng; Qingyi Mu; Yanqiu Leng; Xinghua Zhu; Zhijie Jia; Junyan Zhao; Zhiyuan He; Bingyao Huo; Zekun Li; Jingjing Nan (CATENA, 2025)

Single-chain variable fragment-based immunoassay for bioactive natural products - Xiping Cui; Jian Lu; Jinchao Wei; Suqing Zhao; Yiyong Yan; Guo Yin; Bing Wang; Yunping Mu; Peng Li (Phytochemistry Reviews, 2025)

Corrigendum to “Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain” [Aquaculture, Volume 586, Part 2, 15 February 2025, 741875] - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

UPLC-Q-TOF/MS-based serum metabolomics revealed anti-tumor mechanism of ethanol-soluble acidic components from Camellia oleifera cake and synergy with PD-1 inhibitor - Yixuan Wang; Songyu Yang; Shengbin Chen; Yingbing Zuo; Xiaoyu Mu; Hongmei Zhou; Yufei Yao; Xiaoping Peng; Wenjuan Li (Food Bioscience, 2025)

Enhanced electrochemical performance of NCM811-based batteries by using a multifunctional electrolyte additive - Aijia Wei; Shuxing Mei; Jinping Mu; Peng Liu; Xue Bai; Rui He; Xiaohui Li; Yuxin Niu; Lihui Zhang; Zhenfa Liu; Lei Wang (Chemical Engineering Journal, 2025)

Effects of aquatic Ca2+ and Mg2+ on the antioxidant, immune, osmotic regulation, molting, and metabolic abilities of Scylla paramamosain - Yuntao Li; Chenxi Che; Shan Gao; Kangxiang Qin; Peng Yang; Ziwei Fan; Wenjun Li; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

Integrating machine learning for multi-objective optimization of biomass conversion to hydrogen - Yinchen Li; Peng Jiang; Lin Li; Tuo Ji; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Journal of Cleaner Production, 2025)

Oxygen vacancies enhanced peroxymonosulfate activation by accelerating electron shuttle over carbon-hybrid defective Mn2O3: Mechanistic insight into the singlet oxygen dominated pathway - Yang Xiao; Jincheng Mu; Qiong Peng; Jinming Feng; Bihui Zhou; Nannan Zhang; Baojun Liu (Journal of Environmental Chemical Engineering, 2025)

The impact of organic loading rate on the cultivation and stability of aerobic granular sludge in continuous flow reactor - Yingjian Zhang; Fanchao Meng; Zehan Huang; Minghui Liu; Xuegang Mu; Xuelong Zhang; Guilherme Lelis Giglio; Zhaoxu Peng (International Biodeterioration & Biodegradation, 2025)

Effects of luxS gene on biofilm formation and fermentation property in Lactobacillus plantarum R - Yang Chen; Xin Fan; Xiaoqing Zhu; Junfeng Xiao; Yang Mu; Wenyue Wang; Chao Wang; Mingye Peng; Mengzhou Zhou (Food Research International, 2025)

Optimizing β-Lactoglobulin antigenicity through single enzyme hydrolysis: Exploring structural changes and effects on linear epitopes - Peng Sun; Xiaomeng Wu; Qi Sun; Qing Zhao; Guangqing Mu; Fanhua Kong (Food Chemistry, 2025)

Evaluation of the buffer-blocking capacity of acrocarpous moss Campylopus schmidii as candidate for copper and cadmium migration - Rong Zhang; Feiyun Huang; Zhuang Ju; Bo Mu; Peng Chen (Environmental Research, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Why are the Qinling Mountains Significant to China? - Xing Chen; Yanjun Shen; Qingyi Mu; Panpan Xu; Fenghao Duan; Jianbing Peng (Journal of Earth Science, 2025)

Changes in River Cross-section Morphology and Response to Streamflow and Sediment Processes in Middle Reaches of Yellow River, China - Yongfu Wen; Pengfei Li; Mengzhen Li; Chaohui Ma; Peng Gao; Xingmin Mu; Guangju Zhao (Chinese Geographical Science, 2025)

Exploring the synergistic effect of NaOH/NaClO absorbent in a novel wet FGD scrubber to control SOx/NOx emissions - Muhammad Rizwan; Muhammad Faryad Ali; Muhammad Asif Nawaz; Mu He; Yueqin Song; Peng Jiang; Saif Ullah; Malik M. Abdullah Hassan; Xiaolong Zhou (Environmental Monitoring and Assessment, 2025)

Occurrence and ecological risks of organophosphate esters in the sediments of Hangzhou Bay and the East China Sea - Peng Zhang; Yaqing Cui; Ren Shi; Jing Wang; Linke Ge; Qinglin Mu (Marine Pollution Bulletin, 2025)

Effects of bicarbonate on antioxidant, immune, osmolytic and metabolic capabilities of Scylla paramamosain - Chenxi Che; Yuntao Li; Kangxiang Qin; Ziwei Fan; Wenjun Li; Shan Gao; Peng Yang; Chunlin Wang; Changkao Mu; Huan Wang (Aquaculture, 2025)

AMPK activation by dietary acadesine improves fillet texture in large yellow croaker (Larimichthys crocea) fed a linseed oil-based diet - Shengdi Chen; Zihan Sun; Ningning Liu; Chenbin Yang; Na Li; Lu Li; Chaoqing Wei; Binlun Yan; Huan Gao; Peng Tan; Hua Mu (Aquaculture, 2025)

Mercury isotope evidence for Middle Ordovician photic-zone euxinia: Implications for termination of the Great Ordovician biodiversification event - Mu Liu; Wei Yuan; Chaogang Fang; Xun Wang; Ning Tan; Mingyu Zhao; Xiangli Wang; Thomas J. Algeo; Peng Sun; Xinbin Feng; Daizhao Chen (Gondwana Research, 2025)

The ameliorative effects and underlying mechanisms of Lactobacillus plantarum on glyoxal-induced cytotoxicity - Yang Mu; Siyu Guo; Fangyi Chen; Mingye Peng; Chao Wang; Yang Chen; Mengzhou Zhou (Food Bioscience, 2025)

Influences of freeze-thaw cycles on desiccation cracking of an intact loess - Luqing Zhao; Penghui Ma; Qingyi Mu; Zhijie Jia; Junyan Zhao; Zhiyuan He; Bingyao Huo; Zekun Li; Jianbing Peng (Engineering Geology, 2025)

Moving in the landscape: Omnidirectional connectivity dynamics in China from 1985 to 2020 - Haowei Mu; Shanchuan Guo; Xingang Zhang; Bo Yuan; Zilong Xia; Pengfei Tang; Wei Zhang; Peng Zhang; Xuecao Li; Peijun Du (Environmental Impact Assessment Review, 2025)

An isolate of human blood-associated partitivirus naturally infects the phytopathogenic fungus Bipolaris maydis - Kun Zhang; Ge Mu; Weilan Wu; Peng Wang; Jun Shang; Changquan Li; Qingchao Deng; Shouguo Fang; Haoran Wang; Songbai Zhang (Archives of Virology, 2025)

The Characteristics of Sex Differentiation Based on Morphological Traits During the Early Development Stage of the Swimming Crab Portunus trituberculatus and Sex Prediction Model Comparison - Yanqing Peng; Junkai Lu; Ronghua Li; Chendong Xu; Shangbiao Zheng; Zhiming Ren; Chuan He; Changkao Mu; Weiwei Song; Chunlin Wang (Fishes, 2024)
To investigate the morphological traits of different sexes during the early development stage of the swimming crab Portunus trituberculatus, the genetic sex of 405 crablets from stages C I–V was determined using sex-linked molecular markers. The external appearance of each crab was observed, and the morphological traits, including carapace length (CL), full carapace width (FCW), abdomen width (AW), and abdomen length (AL), were measured to compare the differences between the sexes and to develop non-intrusive methods for sex identification. The genetic sex identification demonstrated that the female-to-male sex ratio at each stage did not deviate from 1:1. The gonopores of the females were first observed at stage C I using a scanning electron microscope; however, the shape difference in the abdominal flap between the sexes from stages C I to stage C V were not observed under a dissecting microscope. Correlation analysis showed that AW3 and AW4 were significantly correlated with sex at stage C V. Three methods were used to predict the sex of the crablets according to the morphological measurements; among them, the multinomial logistic regression (MLR) model performed better than the threshold method or the stepwise discriminant analysis, and the accuracy at stage C V increased to 90% when detailed abdominal parameters were included. These results indicate that it is feasible to predict sex during the early development stages of P. trituberculatus through morphometric and geometric parameters, which would be helpful for the creation of monosex populations of this species.

Impacts of the scale effect on quantifying the response of spring vegetation phenology to urban intensity - Zijie Peng; Dezheng Jiang; Wenbo Li; Qiaoyi Mu; Xuecao Li; Wenting Cao; Zitong Shi; Tuo Chen; Jianxi Huang (Remote Sensing of Environment, 2024)

Variations of soil infiltration in response to vegetation restoration and its influencing factors on the Loess Plateau - Shuyu Zhang; Guangju Zhao; Junjian Fan; Mingyue Yang; Peng Tian; Xingmin Mu; Ren Geng (Journal of Environmental Management, 2024)

Regulation mechanisms of allergenic epitope sites in casein by microbial and plant-derived proteases - Qi Sun; Guangqing Mu; Peng Sun; Qing Zhao; Xiaomeng Wu; Fanhua Kong (Food Bioscience, 2024)

Characterization of a novel heterozygous frameshift variant in NDP gene that causes familial exudative vitreoretinopathy in female patients - Mu Yang; Li Peng; Liting Lv; Erkuan Dai; Yunqi He; Rulian Zhao; Shujin Li (Molecular Genetics and Genomics, 2024)

Chemotaxis gene of a bacterium impacts larval settlement and metamorphosis in the marine mussel Mytilus coruscus via c-di-GMP controlling extracellular protein production - Yu Tao; Jiayi Mu; Lihua Peng; Jin-Long Yang; Xiao Liang (Biofouling, 2024)

SmT/SHM-seq: simultaneously capturing spatial transcriptome and microbiome information in plants - Peng Mu; Weiqiang Li; Lam-Son Phan Tran; Xiangnan Li (Trends in Plant Science, 2024)

The influence of NaCl on xanthate adsorption on chalcopyrite surface and chalcopyrite flotation - Minsu Hwang; Yufan Mu; Liang Cao; Yongjun Peng (Minerals Engineering, 2024)

Permeability characteristics, structural failure characteristics, and triggering process of loess landslides in two typical strata structures - Zekun Li; Penghui Ma; Jianqi Zhuang; Qingyi Mu; Jiaxu Kong; Luqing Zhao; Jianbing Peng (Engineering Geology, 2024)

Multimodal spatiotemporal drug assessment platform based on a microelectrode neural network chip in Alzheimer’s disease - Fan Gao; Wei Xu; Yan Xiao; Wei Jiang; Mu Chen; Zekai Liu; Peng Zhang; Tianyi Yang; Zhiyu Qian; Keqiang Gao (Chemical Engineering Journal, 2024)

Facing the solid waste of cotton straw and plastic mulch film mixture in China: Centralized or decentralized pyrolysis facility? - Hao Zhang; Peng Jiang; Guanhan Zhao; Lin Li; Minjiao Chen; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Waste Management, 2024)

Use of Tirofiban to Prevent Ischemic Events in Patients with CYP2C19 Loss-of-Function Alleles during Flow Diversion of Intracranial Aneurysm: A Multicenter Cohort Study - Yangyang Zhou; Huibin Kang; Wenqiang Li; Bin Luo; Chao Wang; Ruhang Xie; Yongnan Zhu; Qichen Peng; Yisen Zhang; Jian Liu; Ying Zhang; Shiqing Mu; et al. (Translational Stroke Research, 2024)

Exploring Fatty Acid β-Oxidation Pathways in Bacteria: From General Mechanisms to DSF Signaling and Pathogenicity in Xanthomonas - Zhiyong Wang; Xue Hou; Guohui Shang; Guangai Deng; Kai Luo; Mu Peng (Current Microbiology, 2024)

Effect of composite cultivation on the meat quality of crucian carp (Carassius auratus) - Yin Zhang; Yunlong Mu; Linguo Wang; Qing Zeng; Pengcheng Zhang; Haichuan Peng; Qiuyue Chen; Jianlin Jia; Zhongli Pan; Qing Li (Aquaculture International, 2024)

Ammonia monooxygenase-mediated cometabolic biotransformation of volatile 4-chlorophenol in nitrifying counter-diffused biofilms: A combined molecular dynamics simulation, DFT calculation and experimental study - Peng Zheng; Wenqiang Li; Yan Li; Youpeng Cheng; Jing Wang; Yang Mu; Jinyou Shen (Water Research, 2024)

Effect and application of spray drying and freeze drying on characterization of walnut oil microcapsules - Mingming Wang; Hongyu Mu; Lei Peng; Chunlei Tan; Yinyan Chen; Jun Sheng; Yang Tian; Cunchao Zhao (Journal of Food Engineering, 2024)

GmCOL4-GmZTL1 interaction co-regulates GmSBH1 to improve seed deterioration under high temperature and humidity stress and affect leaf development - Kebin Mu; Yingjie Shu; Ming Chen; Keke Chen; Yuxin Peng; Huimin Hu; Yingzi Shen; Xi Zhang; Lifang Zhuang; Hao Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Vegetation factors and atmospheric dryness regulate the dynamics of ecosystem water use efficiency in a temperate semiarid shrubland - Yanmei Mu; Xin Jia; Ziqi Ye; Xulin Guo; Shaorong Hao; Tianshan Zha; Yuqing Zhang; Cong Han; Shengjie Gao; Fei Xing; Shugao Qin; Peng Liu; et al. (Journal of Hydrology, 2024)

Retraction Note: Evaluating an economic application of renewable generated hydrogen: A way forward for green economic performance and policy measures - Baijun Wu; Bingfeng Zhai; Huaizi Mu; Xin Peng; Chao Wang; Ataul Karim Patwary (Environmental Science and Pollution Research, 2024)

Identifying true collectorless flotation of chalcopyrite in calcium chloride solutions - Minsu Hwang; Yufan Mu; Liang Cao; Yongjun Peng (Minerals Engineering, 2024)

The greening of vegetation on the Loess Plateau has resulted in a northward shift of the vegetation greenness line - Xiaoyan Song; Peijun Xie; Wenyi Sun; Xingmin Mu; Peng Gao (Global and Planetary Change, 2024)

Effect of vegetation restoration type and topography on soil water storage and infiltration capacity in the Loess Plateau, China - Dexun Qiu; Ruirui Xu; Peng Gao; Xingmin Mu (CATENA, 2024)

Sediment provenance variations driven by sea level in the eastern Arabian Sea since the MIS 9 period: Evidence from geochemical proxies - Tongbing Fang; Shengfa Liu; Kaikai Wu; Hui Zhang; Peng Cao; Mu Huang; Lina Ai; Wenjing Qi; Jing Tao; Xuefa Shi (Journal of Asian Earth Sciences, 2024)

Pretreatment with rumen fluid improves methane production in the anaerobic digestion of corn straw - Fenglian Xu; Lan Mu; Yifan Wang; Hao Peng; Junyu Tao; Guanyi Chen (Fuel, 2024)

A mutation in CsGME encoding GDP-mannose 3,5-epimerase results in little and wrinkled leaf in cucumber - Mengying Liu; Zhaowei Li; Yunfeng Kang; Jinzhao Lv; Zhuoshuai Jin; Siyu Mu; Hongzhong Yue; Lixia Li; Peng Chen; Yuhong Li (Theoretical and Applied Genetics, 2024)

Probabilistic analysis of the thermal insulation length demand of tunnels in cold regions via the FEM-CFD coupled method - Qionglin Li; Lei Peng; Yanhu Mu; Yanzhi Ji; Dangxian Li (Cold Regions Science and Technology, 2024)

Preparation of iron oxide-modified digestate biochar and effect on anaerobic digestion of kitchen waste - Yifan Wang; Lan Mu; Chen Chen; Fenglian Xu; Hao Peng; Yingjin Song; Guanyi Chen (Bioresource Technology, 2024)

Environmental enrichment improves survival and growth of Portunus trituberculatus in recirculating aquaculture system by reducing energy expenditure and stress responses - Tianhan Xiong; Changkao Mu; Chunlin Wang; Peng Sun; Jie He; Ce Shi; Yangfang Ye (Aquaculture, 2024)

Dry-season length affects the annual ecosystem carbon balance of a temperate semi-arid shrubland - Yanmei Mu; Xin Jia; Ziqi Ye; Tianshan Zha; Xulin Guo; T. Andrew Black; Yuqing Zhang; Shaorong Hao; Cong Han; Shengjie Gao; Shugao Qin; Peng Liu; et al. (Science of The Total Environment, 2024)

Characterizing NOx emissions from diesel trucks with tampered aftertreatment systems and its implications for identifying high emitters - Miao Tian; Liqiang He; Di Peng; Mingliang Fu; Shuai Ma; Jinsong Mu; Quanshun Yu; Jia Wang; Hang Yin; Junfang Wang (Science of The Total Environment, 2024)

Repeat dose and reproductive toxicity of thrombopoietin mimic peptide in Sprague-Dawley rats - Shidong Qiu; Yuji Liang; Xiaobo Wang; Xiue Li; Guoyue Wei; Peng Xiao; Suling Teng; Peilu Sun; Lei Song; Zenglin Zhao; Yanling Mu (Regulatory Toxicology and Pharmacology, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

Genomic features of a plant growth-promoting endophytic Enterobacter cancerogenus JY65 dominant in microbiota of halophyte Suaeda salsa - Mu Peng; Zhihui Jiang; Zhiwen Xiang; Aifen Zhou; Chao Wang; Zhiyong Wang; Fangzhen Zhou (Plant and Soil, 2024)

Contrasting roles of fungal and oomycete pathogens in mediating nitrogen addition and winter grazing effects on biomass - Peng Zhang; Mengjiao Huang; Chaorui Chen; Kui Hu; Junsheng Ke; Mu Liu; Yao Xiao; Xiang Liu (Ecology, 2024)
Both bottom‐up and top‐down processes modulate plant communities. Fungal and oomycete pathogens are most common in global grasslands, and due to differences in their physiology, function, host range, and life cycles, they may differentially affect plants (in both intensity and direction). However, how fungal and oomycete pathogens regulate bottom‐up and top‐down effects on plant community biomass remains unclear. To this end, we conducted a 3‐year field experiment in an alpine meadow incorporating mammalian herbivore exclosure, fungicide/oomyceticide application, and nitrogen addition treatments. We arranged 12 blocks with half randomly assigned to be mammalian herbivore exclosures (fenced to exclude grazing sheep), and the other half were fenced most of the year but not in winter (winter grazing control). Six 2.5 × 2.5 m square plots were established in each block, with each of the six plots assigned as control, nitrogen addition, fungicide application, oomyceticide application, nitrogen addition + fungicide application, and nitrogen addition + oomyceticide application. We found that fungicide application significantly increased plant community biomass (mainly Poaceae species) under nitrogen addition and promoted the bottom‐up effect of nitrogen addition on plant community biomass by altering the community‐weighted mean of plant height (via species turnover). Meanwhile, oomyceticide application significantly increased plant community biomass (mainly Poaceae species) when mammalian herbivores were excluded and weakened the top‐down effect of winter grazing on plant community biomass by driving intraspecific variation in plant height. Our results highlight that fungal and oomycete pathogens play important (but differing) roles in mediating the effects of nutrient availability and higher trophic levels on plant community biomass. Mechanistically, we demonstrated that plant pathogen‐related modulation of plant community biomass is achieved by alterations to plant height. Overall, this study combines both community and disease ecology to reveal complex interactions among higher trophic levels and their potential impacts on terrestrial ecosystem functioning under human disturbance.

Cellular localization and potential ligands of a novel scavenger receptor class B/CD36 protein homolog (Pt-SRB2) identified in the marine crab, Portunus trituberculatus - Su-Ming Zhou; Fang-Mei Lin; Chang-Kao Mu; Chun-Lin Wang; Qi-Cun Zhou; Peng Sun; Fei Yin (Fish & Shellfish Immunology, 2024)

Variation of runoff-sediment relationship at flood event scale in three typical watersheds of the Loess Plateau - Ren Geng; Zixuan Ye; Peng Tian; Qiu Jin; Bo Bi; Guangju Zhao; Xingmin Mu; Tongshun Wang; Dadong Zhu (CATENA, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Importance of habitat heterogeneity in tidal flats to the conservation of migratory shorebirds - Shangxiao Cai; Tong Mu; He‐Bo Peng; Zhijun Ma; David S. Wilcove (Conservation Biology, 2024)
Understanding species distribution patterns and what determines them is critical for effective conservation planning and management. In the case of shorebirds migrating along the East Asian‐Australasian Flyway (EAAF), the loss of stopover habitat in the Yellow Sea region is thought to be the primary reason for the precipitous population declines. However, the rates of decline vary considerably among species, and it remains unclear how such differences could arise within a group of closely related species using apparently similar habitats at the same locales. We mapped the spatial distributions of foraging shorebirds, as well as biotic (benthic invertebrates consumed by migrating shorebirds) and abiotic (sediment characteristics) environmental factors, at a key stopover site in eastern China. Five of the six sediment characteristics showed significant spatial variation with respect to distance along the shoreline or distance from the seawall in the same tidal flat. The biomasses of four of the six most abundant benthic invertebrates were concentrated in the upper or middle zones of the tidal flat. The distribution patterns of all three focal shorebird species on the tidal flat were best explained jointly by this heterogeneity of sediment characteristics and invertebrate prey. These results suggest that the loss of tidal flats along the Yellow Sea, which is typically concentrated at the upper and middle zones, may not only reduce the overall amount of staging habitat, but also disproportionately affect the most resource‐rich portions for the birds. Effective conservation of shorebird staging areas along the EAAF and likely elsewhere must consider the subtle habitat heterogeneity that characterizes these tidal flats, prioritizing the protection of those portions richest in food resources, most frequently used by focal bird species, and most vulnerable to anthropogenic threats. Article impact statement : Heterogeneity of tidal flats with respect to biotic and abiotic factors must be considered in shorebird conservation planning.

Foraging flight-based health indicators for honey bee colonies using automatic monitoring systems - Joe-Air Jiang; Jen-Cheng Wang; Chien-Peng Huang; Mu-Hwa Lee; An-Chi Liu; Hung-Jen Lin; Chien-Hao Wang; Cheng-Ying Chou; En-Cheng Yang (Computers and Electronics in Agriculture, 2024)

The infrastructure cost of permafrost degradation for the Northern Hemisphere - Haodong Jin; Xiaoqing Peng; Oliver W. Frauenfeld; Yuan Huang; Lei Guo; Jing Luo; Guoan Yin; Guohui Zhao; Cuicui Mu (Global Environmental Change, 2024)

Response of runoff-sediment processes to vegetation restoration patterns under different rainfall regimes on the Loess Plateau - Xiaoxue Guo; Min Du; Peng Gao; Peng Tian; Guangju Zhao; Xingmin Mu; Ren Geng (CATENA, 2024)

Relative humidity and solar radiation exacerbate snow drought risk in the headstreams of the Tarim River - Zhixia Wang; Shengzhi Huang; Zhenxia Mu; Guoyong Leng; Weili Duan; Hongbo Ling; Jia Xu; Xudong Zheng; Pei Li; Ziyan Li; Wenwen Guo; Yifei Li; et al. (Atmospheric Research, 2024)

A mutation in CsDWF7 gene encoding a delta7 sterol C-5(6) desaturase leads to the phenotype of super compact in cucumber (Cucumis sativus L.) - Haiqiang Zhang; Zichen Liu; Yunxiao Wang; Siyu Mu; Hongzhong Yue; Yanjie Luo; Zhengao Zhang; Yuhong Li; Peng Chen (Theoretical and Applied Genetics, 2024)

Evaluation of long-term spatio-temporal characteristics of water and nitrogen in the vadose zone and potential threats to groundwater under different irrigation strategies - Jiatun Xu; Qing Mu; Shikun Sun; Nan Yang; Xiongbiao Peng; Yufeng Zou; Shaoyuan Feng; Huanjie Cai (Journal of Cleaner Production, 2023)

Abnormal grey matter structural changes in patients with end-stage kidney disease and mild cognitive impairment: correlations with clinical features - Huijie Yuan; Zhaoyao Luo; Wen Gu; Shaohui Ma; Guangyu Li; Dun Ding; Xueying Ma; Peng Li; Jing Yang; Xiaoling Xu; Junya Mu; Ming Zhang (Metabolic Brain Disease, 2023)
End-stage kidney disease and mild cognitive impairment (ESKD-MCI) affect the quality of life and long-term treatment outcomes of patients affected by these diseases. Clarifying the morphological changes from brain injuries in ESKD-MCI and their relationship with clinical features is helpful for the early identification and intervention of MCI before it progresses to irreversible dementia. This study gathered data from 23 patients with ESKD-MCI, 24 patients with ESKD and non-cognitive impairment (NCI), and 27 health controls (HCs). Structural magnetic resonance studies, cognitive assessments, and general clinical data were collected from all participants. Voxel-based morphometry analysis was performed to compare grey matter (GM) volume differences between the groups. The patients’ GM maps and clinical features were subjected to univariate regression to check for possible correlations. Patients with ESKD-MCI displayed significantly more impairments in multiple cognitive domains, including global cognition, visuospatial and executive function, and memory, compared to patients with ESKD-NCI. Using a more liberal threshold ( P < 0.001, uncorrected), we found that compared to patients with ESKD-NCI, patients with ESKD-MCI exhibited clusters of regions with lower GM volumes, including the right hippocampus (HIP), parahippocampal gyrus (PHG), Rolandic operculum, and supramarginal gyrus. The volumes of the right HIP and PHG were negatively correlated with serum calcium levels. ESKD-MCI was associated with a subtle volume reduction of GM in several brain areas known to be involved in memory, language, and auditory information processing. We speculate that these slight morphometric impairments may be associated with disturbed calcium metabolism.

Optimizing flow regime for the Four Major Chinese Carps by integrating habitat suitability within reservoir operation - Zehao Lv; Gangsheng Wang; Peng Zhang; Xueshan Ai; Xin Cao; Wei Zheng; Zhenyu Mu; Bowen Yu (Journal of Hydrology, 2023)

Historical and projected evolutions of glaciers in response to climate change in High Mountain Asia - Lin Yang; Guangju Zhao; Xingmin Mu; Yanli Liu; Peng Tian; Puqiong; Danzengbandian (Environmental Research, 2023)

Characteristics of secondary inorganic aerosols and contributions to PM2.5 pollution based on machine learning approach in Shandong Province - Tianshuai Li; Qingzhu Zhang; Xinfeng Wang; Yanbo Peng; Xu Guan; Jiangshan Mu; Lei Li; Jiaqi Chen; Haolin Wang; Qiao Wang (Environmental Pollution, 2023)

In situ interfacial engineering modulated adsorption and electron transfer boosting peroxymonosulfate activation for micro-contaminates degradation over CoOx nanosheet - Jinming Feng; Jincheng Mu; Qiong Peng; Yang Xiao; Baojun Liu (Chemical Engineering Journal, 2023)

Insights from Chinese Mariculture Development to Support Global Blue Growth - Daomin Peng; Yongtong Mu; Yugui Zhu; Jiansong Chu; U. Rashid Sumaila (Reviews in Fisheries Science & Aquaculture, 2023)

Estimation of surface ozone concentration over Jiangsu province using a high-performance deep learning model - Xi Mu; Sichen Wang; Peng Jiang; Yanlan Wu (Journal of Environmental Sciences, 2023)

Lactic acid bacteria with probiotic characteristics in fermented dairy products reduce cow milk allergy - Zi-Hao Guo; Qi Wang; Jing-Hong Zhao; Yun-Peng Xu; Guang-Qing Mu; Xue-Mei Zhu (Food Bioscience, 2023)

Biological neutralization of bauxite residue with fermented waste sludge and bio-acid, and the microbial ecological restoration - Dainan Qin; Xiaotong Tan; Xin Zhao; Lulu Qian; Yuanyuan Nie; Xiaolin Pan; Qun Gao; Mu Peng; Yang Liu; Xiaoyu Han (Chemical Engineering Journal, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Dendrobium officinale polysaccharides improved reproductive oxidative stress injury in male mice treated with cyclophosphamide - Yi Mu; Bangwei Che; Kaifa Tang; Wenjun Zhang; Shenghan Xu; Wei Li; Jun He; Miao Liu; Peng Chen; Siwen Zhong; Guangyu Li (Environmental Science and Pollution Research, 2023)

Multi-omics reveals 2-bromo-4,6-dinitroaniline (BDNA)-induced hepatotoxicity and the role of the gut-liver axis in rats - Fuchang Deng; Guangqiu Qin; Yuanyuan Chen; Xu Zhang; Mu Zhu; Min Hou; Qiao Yao; Wen Gu; Chao Wang; Hui Yang; Xudong Jia; Chongming Wu; et al. (Journal of Hazardous Materials, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Synergistic generation mechanisms of SOA and ozone from the photochemical oxidation of 1,3,5-trimethylbenzene: Influence of precursors ratio, temperature and radiation intensity - Hao Zhang; Hong Li; Yujie Zhang; Xuezhong Wang; Fang Bi; Lingshuo Meng; Yunfeng Li; Lu Zhao; Xin Zhang; Zhijian Peng; Yujing Mu; Wahid Mellouki; et al. (Atmospheric Research, 2023)

Endoplasmic reticulum stress: a vital process and potential therapeutic target in chronic obstructive pulmonary disease - Hao Peng; Qing Zhou; Jing Liu; Yi Wang; Ketao Mu; Lei Zhang (Inflammation Research, 2023)

Simultaneous dissolution of nickel, copper and cobalt from low grade nickel matte by (NH4)2S2O8-H2SO4 oxidative leaching - Wenning Mu; Peng Zhong; Mengfei Gu; Weisong Sun; Tengfei Xiao; Hongtao Shen; Haixia Xin; Xuefei Lei; Shaohua Luo; Le Wang (Hydrometallurgy, 2023)

Isolation and characterization of tumorigenic bacteria associated with crown gall disease of Prunus humilis Bunge in China - Rong Xiao; Xiao-Peng Mu; Jian-Cheng Zhang; Shuai Zhang; Chun-Fen Zhang; Shu Deng; Jun-Jie Du; Peng-Fei Wang (European Journal of Plant Pathology, 2023)

Quantifying climate and anthropogenic impacts on runoff using the SWAT model, a Budyko-based approach and empirical methods - Ruirui Xu; Dexun Qiu; Changxue Wu; Xingmin Mu; Guangju Zhao; Wenyi Sun; Peng Gao (Hydrological Sciences Journal, 2023)

An improved YOLOv5-based method for multi-species tea shoot detection and picking point location in complex backgrounds - Luyu Shuai; Jiong Mu; Xueqin Jiang; Peng Chen; Boda Zhang; Hongdan Li; Yuchao Wang; Zhiyong Li (Biosystems Engineering, 2023)

An artificial interfacial layer with biomimetic ionic channels towards highly stable Li metal anodes - Yiju Li; Tianshuai Wang; Junjie Chen; Xudong Peng; Minghui Chen; Bin Liu; Yongbiao Mu; Lin Zeng; Tianshou Zhao (Science Bulletin, 2023)

Visualizing sub-layer structural transformation in carbonized wood tracheid by Raman mapping - Jingjing Xiong; Binbin Xu; Bin Zhang; Peng Jiang; Liwen Mu; Xiaohua Lu; Jiahua Zhu (Fuel, 2023)

Fault detection and calibration for building energy system using Bayesian inference and sparse autoencoder: A case study in photovoltaic thermal heat pump system - Peng Wang; Congwei Li; Ruobing Liang; Sungmin Yoon; Song Mu; Yuchuan Liu (Energy and Buildings, 2023)

Accelerating Li+/Li redox through the regulation of the electric double layer for efficient lithium metal anodes - Tianyi Zhou; Dehuan Shi; Qian Wang; Chengkai Yang; Xiaolong Wang; Kai Wu; Yanlu Mu; Jianyang Wu; Zheyuan Liu; Wen Liu; Henghui Zhou; Peng Jiang (Chemical Engineering Journal, 2023)

Geographical variation in community‐wide herbivory matches patterns of intraspecific variation instead of species turnover - Xiang Liu; Ziyuan Lin; Kui Hu; Xingxing Wang; Peng Zhang; Yao Xiao; Li Zhang; Mu Liu (Global Ecology and Biogeography, 2023)
Aim Attempts over the past 30 years to explain geographical variation in the strength of herbivore pressure have given rise to ecological hypotheses like the latitudinal herbivory hypothesis. This hypothesis, however, has rarely been tested using community‐level data. Therefore, the aim of our study was to examine the patterns and potential mechanisms underlying geographical variation in community‐wide herbivory. Location The Qinghai‐Tibetan Plateau. Time Period July 2021. Major Taxa Studied Plants. Methods We selected 43 grassland sites along a 1500‐km latitudinal gradient ( c . 27°N to 39°N) and a 2698‐m elevational gradient (1886–4584 m) on the Qinghai‐Tibetan Plateau. We evaluated geographical patterns in invertebrate herbivory pressure at the population and community levels, while also evaluating the importance of geographical variation in mediating the effects of abiotic and biotic factors on intraspecific variation (through changes in herbivory on component species) and species turnover effects (through changes in plant community composition). Results Community‐wide herbivory decreased with latitude, mirroring intraspecific variation, while species turnover effects did not vary along any tested geographical gradients. Furthermore, we found that geographical variation in community‐wide herbivory was strongly positively correlated with soil nitrogen content. We also found a positive effect of soil nitrogen content on intraspecific variation and a negative effect of plant community biomass on species turnover effects. Main Conclusions The latitudinal gradient in community‐wide herbivory was primarily mediated by intraspecific variation, which was in turn associated with a gradient in soil nitrogen content. Our findings highlight the need for community‐wide assessments of geographical variation in plant–herbivore interactions, decomposing community‐wide herbivory into intraspecific variation and species turnover effects.

Remediation and recovery of Kariba weed as emerging contaminant in freshwater and shellfish aquaculture system via solvothermal liquefaction - Elfina Azwar; Wan Adibah Wan Mahari; Rock Keey Liew; Muhammad Zulhilmi Ramlee; Meenakshi Verma; William Woei Fong Chong; Wanxi Peng; Hui Suan Ng; Mu. Naushad; Christian Sonne; Su Shiung Lam (Science of The Total Environment, 2023)

Mechanistic insights into dissolved organic matter-driven protistan and bacterial community dynamics influenced by vegetation restoration - Zhang-mu Jing; Qing-qian Li; Yan-jie Wei; Bin Dong; Peng Yuan; Rui-xia Liu; Hong-jie Gao (Environmental Research, 2023)

Response of soil erosion to vegetation restoration and terracing on the Loess Plateau - Peng Tian; Xiaojing Tian; Ren Geng; Guangju Zhao; Lin Yang; Xingmin Mu; Peng Gao; Wenyi Sun; Yulin Liu (CATENA, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

A novel photochemical conversion technique for reliable calibration of peroxyacetyl nitrate (PAN) analyzers - Xiaowei He; Chenglong Zhang; Pengfei Liu; Gen Zhang; Hai Wu; Yuexiang Peng; Junfeng Liu; Chengtang Liu; Yujing Mu (Science of The Total Environment, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Maximise pyrite depression in copper ore flotation using high salinity water - Yufan Mu; Yongjun Peng (Minerals Engineering, 2023)

Sediment source tracing during flood events in the Huangfu River basin in the northern Loess Plateau, China - Xiaojing Tian; Peng Tian; Guangju Zhao; José A. Gómez; Jianying Guo; Xingmin Mu; Peng Gao; Wenyi Sun (Journal of Hydrology, 2023)

Effects of cascading reservoirs on streamflow and sediment load with machine learning reconstructed time series in the upper Yellow River basin - Junjian Fan; Guangju Zhao; Xingmin Mu; Ang Lu; Peng Tian; Peng Gao; Wenyi Sun (CATENA, 2023)

Impact of Climate Change on Water Transfer Scale of Inter-basin Water Diversion Project - Tao Bai; Lei Li; Peng-fei Mu; Bao-zhu Pan; Jin Liu (Water Resources Management, 2023)

High carbon emissions from thermokarst lakes and their determinants in the Tibet Plateau - Cuicui Mu; Mei Mu; Xiaodong Wu; Lin Jia; Chenyan Fan; Xiaoqing Peng; Chien‐Lu Ping; Qingbai Wu; Cunde Xiao; Jianbao Liu (Global Change Biology, 2023)
Thermokarst lakes are potentially important sources of methane (CH 4 ) and carbon dioxide (CO 2 ). However, considerable uncertainty exists regarding carbon emissions from thermokarst lakes owing to a limited understanding of their patterns and motivators. In this study, we measured CH 4 and CO 2 diffusive fluxes in 163 thermokarst lakes in the Qinghai–Tibet Plateau (QTP) over 3 years from May to October. The median carbon emissions from the QTP thermokarst lakes were 1440 mg CO 2 m −2 day −1 and 60 mg CH 4 m −2 day −1 , respectively. The diffusive rates of CO 2 and CH 4 are related to the catchment land cover type. Sediment microbial abundance and hydrochemistry explain 51.9% and 38.3% of the total variance in CH 4 diffusive emissions, respectively, while CO 2 emissions show no significant relationship with environmental factors. When upscaling carbon emissions from the QTP thermokarst lakes, the annual average CH 4 release per lake area is equal to that of the pan‐Arctic region. Our findings highlight the importance of incorporating in situ observation data with different emission pathways for different land cover types in predicting carbon emissions from thermokarst lakes in the future.

Impact of antibiotics on microbial community in aquatic environment and biodegradation mechanism: a review and bibliometric analysis - Xiaoying Mu; Zhihua Huang; Okugbe Ebiotubo Ohore; Jinjin Yang; Kai Peng; Shaokang Li; Xiang Li (Environmental Science and Pollution Research, 2023)

Gully erosion and expansion mechanisms in loess tablelands and the scientific basis of gully consolidation and tableland protection - Zhao Jin; Jianbing Peng; Jianqi Zhuang; Li Feng; Aidi Huo; Xingmin Mu; Wenlong Wang (Science China Earth Sciences, 2023)

Canopy greenness, atmospheric aridity, and large rain events jointly regulate evapotranspiration partitioning in a temperate semiarid shrubland - Shaorong Hao; Xin Jia; Yanmei Mu; Tianshan Zha; Shugao Qin; Peng Liu; Yun Tian; Jiandong Qi; Hongxian Zhao; Xinhao Li (Agricultural and Forest Meteorology, 2023)

Performance and changes of high‐resolution (1 km) surface air temperature in Northern Hemisphere permafrost regions - Haodong Jin; Xiaoqing Peng; Oliver W. Frauenfeld; Yaohua Zhao; Xuanjia Li; Weiwei Tian; Cong Chen; Benben Liang; Xiaodong Li; Cuicui Mu (International Journal of Climatology, 2023)
Surface air temperatures are significant indicators of environmental and climatic change that affect a diverse set of physical systems including permafrost. Most temperature products, such as gridded or reanalysis data, are still at a relatively low spatial resolution, limiting the ability to simulate heterogeneous permafrost changes and leading to large uncertainties. Here we apply a downscaling method based on elevation to obtain high‐resolution surface air temperatures from the sixth Coupled Model Intercomparison Project in Northern Hemisphere permafrost regions. Root‐mean‐square errors and mean absolute errors after downscaling are reduced by 34 and 37%, respectively, relative to meteorological site data and gridded observations from the Climatic Research Unit. Compared to the downscaled surface air temperature data, nondownscaled model projections overestimate by 0.12–0.39°C in the discontinuous, isolated, and sporadic permafrost regions and underestimate up to 0.18°C in the continuous permafrost region under different emission scenarios. The warming rates in Northern Hemisphere permafrost regions were 0.093°C/10 year during the historical (1850–2014) period and are projected to be 0.22°C/10 year for SSP1‐2.6, 0.48°C/10 year for SSP2‐4.5, 0.75°C/10 year for SSP3‐7.0, and 0.95°C/10 year for SSP5‐8.5 during 2015–2100, which is 1.4–1.6 times the warming of nonpermafrost regions. Warming rates in high latitudes are 1.2–1.7 times higher than those in high‐elevation regions. Continuous permafrost regions' warming will be 1.2–1.4 times higher than in other permafrost regions. For permafrost with high ground ice content, warming will be 1.1 times greater than in permafrost regions with medium or low ground ice content.

Failure mechanism and movement process of three loess landslides due to freeze-thaw cycle in the Fangtai village, Yongjing County, Chinese Loess Plateau - Jiaxu Kong; Jianqi Zhuang; Jianbing Peng; Penghui Ma; Jiewei Zhan; Jiaqi Mu; Jie Wang; Dan Zhang; Jia Zheng; Yuting Fu; Shibao Wang; Chenhui Du (Engineering Geology, 2023)

Drought trigger thresholds for different levels of vegetation loss in China and their dynamics - Wenwen Guo; Shengzhi Huang; Qiang Huang; Guoyong Leng; Zhenxia Mu; Zhiming Han; Xiaoting Wei; Dunxian She; Hanye Wang; Zhixia Wang; Jian Peng (Agricultural and Forest Meteorology, 2023)

Relationship between sediment load and climate extremes in the major Chinese rivers - Yatong Zhang; Peng Tian; Lin Yang; Guangju Zhao; Xingmin Mu; Bing Wang; Pengfei Du; Peng Gao; Wenyi Sun (Journal of Hydrology, 2023)

Ammonium-free and grain-protection deliming technology with the combination of aromatic sulfonic acid and sodium dihydrogen phosphate in leather manufacture - Chunxiao Zhang; Ting Liu; Baosheng Huang; Xu Zhang; Biyu Peng; Changdao Mu (Journal of Cleaner Production, 2023)

Effect of 4 °C and ice temperature on umami-enhancing nucleotides of conditioned pork - Yin Zhang; Yingjie Zhang; Hui Li; Ting Bai; Qin Qian; Haichuan Peng; Yunlong Mu; Linguo Wang; Baohua Liu; Jie Chen; Zhongli Pan; Dayu Liu; et al. (Food Chemistry, 2023)

Effects of vegetation restoration on soil infiltrability and preferential flow in hilly gully areas of the Loess Plateau, China - Dexun Qiu; Ruirui Xu; Changxue Wu; Xingmin Mu; Guangju Zhao; Peng Gao (CATENA, 2023)

Reduced graphene oxide/carbon nitride composite sponge for interfacial solar water evaporation and wastewater treatment - He Zhang; Lele Li; Le Geng; Xinyan Tan; Yaxuan Hu; Peng Mu; Jian Li (Chemosphere, 2023)

Mobilization of water affecting formation and dissociation of hydrate in clay sediment - Peng Zhang; Xueping Chen; Lianhai Zhang; Shuaijun Li; Wenting Chen; Qingbai Wu; Shuanshi Fan; Rui Bao; Cuicui Mu (Chemical Engineering Journal, 2023)

Linkages between soil erosion and long-term changes of landscape pattern in a small watershed on the Chinese Loess Plateau - Chaoliang Chen; Guangju Zhao; Yatong Zhang; Yunpeng Bai; Peng Tian; Xingmin Mu; Xiaojing Tian (CATENA, 2023)

Effects of sponge iron dosage on nitrogen removal performance and microbial community structure in sequencing batch reactors - Hongjuan Zhu; Wenxuan Li; Xinjuan Chen; Hao Mu; Kaiyao Hu; Shuang Ren; Yuzhuo Peng; Ruifeng Zhao; Yae Wang (Bioresource Technology, 2023)

Responses of seven wetlands carbon sources and sinks to permafrost degradation in Northeast China - Lidong Han; Changcheng Mu; Ning Jiang; Zhongqi Shen; Yihui Chang; Li Hao; Wenhong Peng (Journal of Soils and Sediments, 2023)

Is China’s Fishing Capacity Management Sufficient? Quantitative Assessment of China’s Efforts toward Fishing Capacity Management and Proposals for Improvement - Hyun-Joo Yang; Daomin Peng; Honghong Liu; Yongtong Mu; Do-Hoon Kim (Journal of Marine Science and Engineering, 2022)
As the country with the world’s largest fishing capacity, China suffers from the depletion of living marine resources, mainly caused by overexploitation, the effects of which also distinctly influence global sustainable utilization of marine resources and maritime order. The country has implemented a series of measures to control its national fishing capacity, notably since the late 1980s, and strongly expressed its responsibility and commitment to sustainable resource utilization in the 13th Five-Year Plan (2016–2020). This study quantitatively assesses the effect of China’s fishing capacity management efforts by examining changes in the fishing capacity of marine capture fisheries by region from 1979 to 2019 in Chinese waters, based on window data envelopment analysis (DEA), and further proposes directions for policy adjustment. The results suggest that China’s coastal and offshore fisheries are still subject to overcapacity of approximately 20%, despite major corrective efforts invested in past decades. This implies that China needs to further improve its fishing capacity management and set clear objectives, as determined by the availability of resources and regional features. Global fisheries management’s focus is shifting from input to output control, but overcapacity still threatens the sustainable use of fisheries resources in China and poses obstacles to other systems.

Exotic fishes that are phylogenetically close but functionally distant to native fishes are more likely to establish - Meng Xu; Shao‐peng Li; Jaimie T. A. Dick; Dangen Gu; Miao Fang; Yexin Yang; Yinchang Hu; Xidong Mu (Global Change Biology, 2022)
Since Darwin's time, degree of ecological similarity between exotic and native species has been assumed to affect the establishment success or failure of exotic species. However, a direct test of the effect of exotic–native similarity on establishment of exotics is scarce because of the difficulty in recognizing failures of species to establish in the field. Here, using a database on the establishment success and failure of exotic fish species introduced into 673 freshwater lakes, we evaluate the effect of similarity on the establishment of exotic fishes by combining phylogenetic and functional information. We illustrate that, relative to other biotic and abiotic factors, exotic–native phylogenetic and functional similarities were the most important correlates of exotic fish establishment. While phylogenetic similarity between exotic and resident fish species promoted successful establishment, functional similarity led to failure of exotics to become established. Those exotic species phylogenetically close to, but functionally distant from, native fishes were most likely to establish successfully. Our findings provide a perspective to reconcile Darwin's naturalization conundrum and suggest that, while phylogenetic relatedness allows exotic fish species to pre‐adapt better to novel environments, they need to possess distinct functional traits to reduce competition with resident native fish species.

Xinfangfangia pollutisoli sp. nov., Isolated from Clopyralid-Contaminated Soil - Yang Mu; Jia-Yi Peng; Hui-Ping Wang; Yue Song; Hong-Mei Wang; Qing Chen; Kai Chen (Current Microbiology, 2022)

A 215-bp indel at intron I of BoFLC2 affects flowering time in Brassica oleracea var. capitata during vernalization - Qinfei Li; Ao Peng; Jiaqin Yang; Sidi Zheng; Zhangping Li; Yinhui Mu; Lei Chen; Jun Si; Xuesong Ren; Hongyuan Song (Theoretical and Applied Genetics, 2022)

Changes in extreme precipitation in the Wei River Basin of China during 1957–2019 and potential driving factors - Dexun Qiu; Changxue Wu; Xingmin Mu; Guangju Zhao; Peng Gao (Theoretical and Applied Climatology, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

A Proposed Scheme of Fishing Quota Allocation to Ensure the Sustainable Development of China’s Marine Capture Fisheries - Honghong Liu; Daomin Peng; Hyun-Joo Yang; Yongtong Mu; Yugui Zhu (Frontiers in Marine Science, 2022)
The sustainable development of marine capture fisheries (MCFs) plays a significant role in food security, economic development, and employment stability. The lack of information on the sustainability of MCFs, along with the inadequate management of fisheries output controls, has weakened China’s efforts towards a national catch limit target of no more than 10 million tons from capture fisheries until 2020. Furthermore, overfishing and fishery conflicts still exist. In order to try and resolve the above problems and achieve the sustainable use of fishery resources, an evaluation of the development status of these fisheries based on the coupling coordination model has been undertaken. The results show that the social, economic, and biological systems of MCFs in coastal areas of China interact with each other while their development is not coordinated, and regional differences exist. This study integrates the socioeconomic indicators using the catch-share program as a breakthrough methodology to resolve inconsistencies. The results under different allocation schemes suggest that the multifactor scheme is more equitable than the single-factor scheme, which enhances the fairness of the initial distribution.

Spatial-temporal Analysis and Prediction of Precipitation Extremes: A Case Study in the Weihe River Basin, China - Dexun Qiu; Changxue Wu; Xingmin Mu; Guangju Zhao; Peng Gao (Chinese Geographical Science, 2022)

Simultaneous detection of ten kinds of insecticide residues in honey and pollen using UPLC-MS/MS with graphene and carbon nanotubes as adsorption and purification materials - Xiuyu Pang; Chenyu Li; Chuanjiang Zang; Lei Guan; Peng Zhang; Chunxiang Di; Nan Zou; Beixing Li; Wei Mu; Jin Lin (Environmental Science and Pollution Research, 2022)

Delineating the Decussating Dentato-rubro-thalamic Tract and Its Connections in Humans Using Diffusion Spectrum Imaging Techniques - Si-Qi Ou; Peng-Hu Wei; Xiao-Tong Fan; Yi-He Wang; Fei Meng; Mu-Yang Li; Yong-Zhi Shan; Guo-Guang Zhao (The Cerebellum, 2022)

RETRACTED ARTICLE: Evaluating an economic application of renewable generated hydrogen: A way forward for green economic performance and policy measures - Baijun Wu; Bingfeng Zhai; Huaizi Mu; Xin Peng; Chao Wang; Ataul Karim Patwary (Environmental Science and Pollution Research, 2022)

Comparative phylogeography of Acanthocalyx (Caprifoliaceae) reveals distinct genetic structures in the Himalaya–Hengduan Mountains - Qi-Yong Mu; Chih-Chieh Yu; Yan Wang; Ting-Shen Han; Hui Wang; Wen-Na Ding; Qiu-Yue Zhang; Shook Ling Low; Quan-Jing Zheng; Chuan Peng; Zheng-Yan Hu; Yao-Wu Xing (Alpine Botany, 2022)

A landslide in Heifangtai, northwest of the Chinese Loess Plateau: triggered factors, movement characteristics, and failure mechanism - Jia-xu Kong; Jian-qi Zhuang; Jie-wei Zhan; Zheng-wei Bai; Yan-qiu Leng; Peng-hui Ma; Jian-bing Peng; Zuo-peng Wang; Tian-feng Gu; Jia-xing Sun; Fan-chen Zhang; Yuan-jun Xu; et al. (Landslides, 2021)

Contributions of climate change and human activities to runoff and sediment discharge reductions in the Jialing River, a main tributary of the upper Yangtze River, China - Yiting Shao; Yi He; Xingmin Mu; Guangju Zhao; Peng Gao; Wenyi Sun (Theoretical and Applied Climatology, 2021)

White matter characteristics between amygdala and prefrontal cortex underlie depressive tendency in end stage renal disease patients before the dialysis initiation - Junya Mu; Liang Ma; Dun Ding; Xueying Ma; Peng Li; Ruixiao Li; Ming Zhang; Jixin Liu (Brain Imaging and Behavior, 2021)

The Price Difference and Trend Analysis of Yesso Scallop (Patinopecten yessoensis) in Changhai County, China - Daomin Peng; Qian Yang; Yongtong Mu; Hongzhi Zhang (Journal of Marine Science and Engineering, 2021)
This paper focuses on the difference in inter-group and intra-group price of Yesso scallop (Patinopecten yessoensis) and the simulation accuracy of three different exponential smoothing models in the price. Based on the farm-gate price and wholesale price data of P. yessoensis in Changhai county from January 2017 to December 2018, this study uses the Wilcoxon rank sum test to compare the inter- and intra-group price and applies simple exponential smoothing (SES), Holt’s linear trend method, and Holt-Winters’ additive method to simulate and predict the price. The results suggest that (i) to improve economic benefits, it is necessary to formulate reasonable farming area and establish low-density ecological cultivation mode; (ii) the price’s Akaike information criterion (AIC) and mean absolute percentage error (MAPE) values by the SES model are optimal, and the MAPE value is lower than 4%; and (iii) the result of SES analysis shows no obvious change from January to March 2019.

The regulation of the small-conductance calcium-activated potassium current and the mechanisms of sex dimorphism in J wave syndrome - Mu Chen; Yudong Fei; Tai-Zhong Chen; Yi-Gang Li; Peng-Sheng Chen (Pflügers Archiv - European Journal of Physiology, 2021)

Association of FMO3 rs1736557 polymorphism with clopidogrel response in Chinese patients with coronary artery disease - Kong-Xiang Zhu; Pei-Yuan Song; He-Li; Mu-Peng Li; Yin-xiao Du; Qi-lin Ma; Li-Ming Peng; Xiao-Ping Chen (European Journal of Clinical Pharmacology, 2021)

QTL mapping and validation of bread wheat flag leaf morphology across multiple environments in different genetic backgrounds - Yang Tu; Hang Liu; Jiajun Liu; Huaping Tang; Yang Mu; Mei Deng; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2021)

Dissection and validation of a QTL cluster linked to Rht-B1 locus controlling grain weight in common wheat (Triticum aestivum L.) using near-isogenic lines - Panfeng Guan; Xueyi Shen; Qing Mu; Yongfa Wang; Xiaobo Wang; Yongming Chen; Yue Zhao; Xiyong Chen; Aiju Zhao; Weiwei Mao; Yiwen Guo; Mingming Xin; et al. (Theoretical and Applied Genetics, 2020)

A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus - Li-Hua Peng; Xiao Liang; Rui-Heng Chang; Jia-Yi Mu; Hui-E Chen; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2020)

Characteristics and health risk assessments of heavy metals in PM2.5 in Taiyuan and Yuci college town, China - Xiaofeng Liu; Zhilei Wang; Huiling Bai; Shuting Zhang; Ling Mu; Lin Peng (Air Quality, Atmosphere & Health, 2020)

MiR-34a suppresses osteoblast differentiation through glycolysis inhibition by targeting lactate dehydrogenase-A (LDHA) - Mu Hong; Xiao-Bin Zhang; Fei Xiang; Xu Fei; Xue-Lian Ouyang; Xiao-Chun Peng (In Vitro Cellular & Developmental Biology - Animal, 2020)

Acceleration of thaw slump during 1997–2017 in the Qilian Mountains of the northern Qinghai-Tibetan plateau - Cuicui Mu; Jianguo Shang; Tingjun Zhang; Chengyan Fan; Shufa Wang; Xiaoqing Peng; Wen Zhong; Feng Zhang; Mei Mu; Lin Jia (Landslides, 2020)

MiRNA-211 triggers an autophagy-dependent apoptosis in cervical cancer cells: regulation of Bcl-2 - Shang Liu; Hongyan Wang; Jing Mu; Hao Wang; Yan Peng; Qi Li; Dongwei Mao; Liyuan Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Distinguishing the effects of vegetation restoration on runoff and sediment generation on simulated rainfall on the hillslopes of the loess plateau of China - Chaojun Gu; Xingmin Mu; Peng Gao; Guangju Zhao; Wenyi Sun; Xuejin Tan (Plant and Soil, 2020)

The variation of motor-related brain structure and its relation to abnormal motor behaviors in end-stage renal disease patients with restless legs syndrome - Junya Mu; Xiaohui Liu; Shaohui Ma; Tao Chen; Xueying Ma; Peng Li; Dun Ding; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2020)

Quantifying the impacts of human activities on runoff and sediment load changes in a Loess Plateau catchment, China - Jinfei Hu; Guangju Zhao; Xingmin Mu; Peng Tian; Peng Gao; Wenyi Sun (Journal of Soils and Sediments, 2019)

MicroRNA transcriptome analysis of poly I:C-stimulated and PRRSV-infected porcine alveolar macrophages - Junjing Wu; Ziyun Ji; Mu Qiao; Xianwen Peng; Huayu Wu; Zhongxu Song; Haizhong Zhao; Guisheng Liu; Fenge Li; Shuqi Mei (Journal of Applied Genetics, 2019)

Anti-breast cancer triterpenoid saponins from the thorns of Gleditsia sinensis - Jinqian Yu; Gang Li; Yan Mu; Honglei Zhou; Xiao Wang; Peng Yang (Natural Product Research, 2019)

Use of near-isogenic lines to precisely map and validate a major QTL for grain weight on chromosome 4AL in bread wheat (Triticum aestivum L.) - Panfeng Guan; Na Di; Qing Mu; Xueyi Shen; Yongfa Wang; Xiaobo Wang; Kuohai Yu; Wanjun Song; Yongming Chen; Mingming Xin; Zhaorong Hu; Weilong Guo; et al. (Theoretical and Applied Genetics, 2019)

Rainfall erosivity and sediment load over the Poyang Lake Basin under variable climate and human activities since the 1960s - Chaojun Gu; Xingmin Mu; Peng Gao; Guangju Zhao; Wenyi Sun; Qiang Yu (Theoretical and Applied Climatology, 2019)

Influence of vegetation restoration on soil physical properties in the Loess Plateau, China - Chaojun Gu; Xingmin Mu; Peng Gao; Guangju Zhao; Wenyi Sun; John Tatarko; Xuejin Tan (Journal of Soils and Sediments, 2019)

Efficiency of sequential UV/H2O2 and biofilm process for the treatment of secondary effluent - Peng-Fei Yan; Shoujun Yuan; Wei Wang; Zhen-Hu Hu; Yang Mu; Han-Qing Yu (Environmental Science and Pollution Research, 2019)

Nonomuraea rhizosphaerae sp. nov., an actinomycete isolated from the rhizosphere soil of a rubber tree (Hevea brasiliensis Muell. Arg) - Junwei Zhao; Shan Mu; Qiannan Zhao; Shanwen Jiang; Peng Cao; Xiaowei Guo; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

Variations in extreme precipitation on the Loess Plateau using a high-resolution dataset and their linkages with atmospheric circulation indices - Guangju Zhao; Jianqing Zhai; Peng Tian; Limei Zhang; Xingmin Mu; Zhengfeng An; Mengwei Han (Theoretical and Applied Climatology, 2018)

Abnormal interaction between cognitive control network and affective network in patients with end-stage renal disease - Junya Mu; Tao Chen; Qianqian Liu; Dun Ding; Xueying Ma; Peng Li; Anmao Li; Mingxia Huang; Zengjun Zhang; Jixin Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

Long non-coding RNA (lncRNA) MAGI2-AS3 inhibits breast cancer cell growth by targeting the Fas/FasL signalling pathway - Yong Yang; Hong Yang; Miao Xu; Haibin Zhang; Mingtao Sun; Peng Mu; Tongbao Dong; Shanmei Du; Kui Liu (Human Cell, 2018)

Roles of flotillins in tumors - Xu-xu Liu; Wei-dong Liu; Lei Wang; Bin Zhu; Xiao Shi; Zi-xuan Peng; He-cheng Zhu; Xing-dong Liu; Mei-zuo Zhong; Dan Xie; Mu-sheng Zeng; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2018)

Accuracy evaluation of the crop-weather yield predictive models of Italian ryegrass and forage rye using cross-validation - Jing-Lun Peng; Moon-Ju Kim; Mu-Hwan Jo; Doo-Hong Min; Kyung-Dae Kim; Bae-Hun Lee; Byong-Wan Kim; Kyung-Il Sung (Journal of Crop Science and Biotechnology, 2017)

Synergistic effects of temperature and humidity on the symptoms of COPD patients - Zhe Mu; Pei-Li Chen; Fu-Hai Geng; Lei Ren; Wen-Chao Gu; Jia-Yun Ma; Li Peng; Qing-Yun Li (International Journal of Biometeorology, 2017)

Effects of climate change and human activities on runoff and sediment inputs of the largest freshwater lake in China, Poyang Lake - Chaojun Gu; Xingmin Mu; Peng Gao; Guangju Zhao; Wenyi Sun; Pengfei Li (Hydrological Sciences Journal, 2017)

Variations in soil moisture over the ‘Huang-Huai-Hai Plain’ in China due to temperature change using the CNOP-P method and outputs from CMIP5 - GuoDong Sun; Fei Peng; Mu Mu (Science China Earth Sciences, 2017)

Changes of soil thermal and hydraulic regimes in the Heihe River Basin - Xiaoqing Peng; Cuicui Mu (Environmental Monitoring and Assessment, 2017)

A method for alpine wetland delineation and features of border: Zoigê Plateau, China - Yaomin Zheng; Zhenguo Niu; Peng Gong; Mengna Li; Lile Hu; Lei Wang; Yuxiang Yang; Haijun Gu; Jinrong Mu; Gejia Dou; Hui Xue; Lin Wang; et al. (Chinese Geographical Science, 2017)

Effects of check dams on runoff and sediment load in a semi-arid river basin of the Yellow River - Erhui Li; Xingmin Mu; Guangju Zhao; Peng Gao; Wenyi Sun (Stochastic Environmental Research and Risk Assessment, 2017)

Human activity and climate variability impacts on sediment discharge and runoff in the Yellow River of China - Yi He; Fei Wang; Xingmin Mu; Lanqin Guo; Peng Gao; Guangju Zhao (Theoretical and Applied Climatology, 2017)

Changes in daily and monthly rainfall in the Middle Yellow River, China - Yi He; Peng Tian; Xingmin Mu; Peng Gao; Guangju Zhao; Fei Wang; Pengfei Li (Theoretical and Applied Climatology, 2017)

Repeated Neonatal Sevoflurane Exposure-Induced Developmental Delays of Parvalbumin Interneurons and Cognitive Impairments Are Reversed by Environmental Enrichment - Mu-huo Ji; Zhong-yun Wang; Xiao-ru Sun; Hui Tang; Hui Zhang; Min Jia; Li-li Qiu; Guang-fen Zhang; Yong G. Peng; Jian-jun Yang (Molecular Neurobiology, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

The Effect of Land Use on Bacterial Communities in Saline–Alkali Soil - Mu Peng; Hongbai Jia; Qiuyu Wang (Current Microbiology, 2017)

Non-integrating lentiviral vectors based on the minimal S/MAR sequence retain transgene expression in dividing cells - Zhen Xu; Feng Chen; Lingling Zhang; Jing Lu; Peng Xu; Guang Liu; Xuemin Xie; Wenli Mu; Yajun Wang; Depei Liu (Science China Life Sciences, 2016)

Methyl jasmonate regulated diploid and tetraploid black locust (Robinia pseudoacacia L.) tolerance to salt stress - Mingquan Jiang; Fuling Xu; Mu Peng; Fenglan Huang; Fanjuan Meng (Acta Physiologiae Plantarum, 2016)

Measurements of nitrous acid (HONO) in urban area of Shanghai, China - François Bernard; Mathieu Cazaunau; Benoît Grosselin; Bin Zhou; Jun Zheng; Peng Liang; Yujie Zhang; Xingnan Ye; Véronique Daële; Yujing Mu; Renyi Zhang; Jianmin Chen; et al. (Environmental Science and Pollution Research, 2016)

Sublethal concentration of benzothiazole adversely affect development, reproduction and longevity of Bradysia odoriphaga (Diptera: Sciaridae) - Yunhe Zhao; Peng Zhang; Yongbiao Zhai; Chengyu Chen; Qiuhong Wang; Jingkun Han; Zhengqun Zhang; Feng Liu; Wei Mu (Phytoparasitica, 2016)

Health risk assessment of toxic VOCs species for the coal fire well drillers - Yulong Yan; Lin Peng; Na Cheng; Huiling Bai; Ling Mu (Environmental Science and Pollution Research, 2015)

Characteristics of hopanoid hydrocarbons in ambient PM10 and motor vehicle emissions and coal ash in Taiyuan, China - Feng Han; Junji Cao; Lin Peng; Huiling Bai; Dongmei Hu; Ling Mu; Xiaofeng Liu (Environmental Geochemistry and Health, 2015)

Isolation and detection of transcript-derived fragments (TDFs) in NaCl-stressed black locust (Robinia pseudoacacia L.) using cDNA-AFLP analysis - Fuling Xu; Mu Peng; Qiuxiang Luo; Mingquan Jiang; Xiuli Zhang; Xianchun Zong; Fanjuan Meng; Yajun Li (Acta Physiologiae Plantarum, 2015)

Determination of the potential illegal addition of β-blockers to function foods by QuEChERS sample preparation and UPLC-MS/MS analysis - Jingchuan Shang; Xiaoqin He; Cunxian Xi; Bobin Tang; Guomin Wang; Dongdong Chen; Tao Peng; Zhaode Mu (Food Additives & Contaminants: Part A, 2015)

Changing trends and regime shift of streamflow in the Yellow River basin - Guangju Zhao; Erhui Li; Xingmin Mu; Zhongming Wen; Scott Rayburg; Peng Tian (Stochastic Environmental Research and Risk Assessment, 2015)

Water use efficiency of net primary production in global terrestrial ecosystems - Lei Xia; Fei Wang; Xingmin Mu; Kai Jin; Wenyi Sun; Peng Gao; Guangju Zhao (Journal of Earth System Science, 2015)

Detection of inherited mutations for hereditary cancer using target enrichment and next generation sequencing - Yanfang Guan; Hong Hu; Yin Peng; Yuhua Gong; Yuting Yi; Libin Shao; Tengfei Liu; Gairui Li; Rongjiao Wang; Pingping Dai; Yves-Jean Bignon; Zhe Xiao; et al. (Familial Cancer, 2015)

Comparison of Bradysia odoriphaga Yang and Zhang reared on artificial diet and different host plants based on an age-stage, two-sex life table - Peng Zhang; Feng Liu; Wei Mu; Qiuhong Wang; Hui Li (Phytoparasitica, 2015)

Degradation characteristics of permafrost under the effect of climate warming and engineering disturbance along the Qinghai–Tibet Highway - Hui Peng; Wei Ma; Yan-hu Mu; Long Jin; Kun Yuan (Natural Hazards, 2015)

Domesticated honey bees evolutionarily reduce flower nectar volume in a Tibetan lotus - Junpeng Mu; Youhong Peng; Xinqiang Xi; Xinwei Wu; John N. Griffin; Karl J. Niklas; Shucun Sun (Ecology, 2014)
Plants have evolved costly flowering traits, including the provisioning of rich nectar, to attract and reward their pollinators. Beekeeping (apiculture) locally increases densities of honey bees, which might drive economization of pollinator‐attracting traits, but the potential evolutionary consequences of beekeeping on plant–pollinator interactions remain unknown. Here, we present evidence suggesting that intensive apiculture has driven the rapid evolution of plant traits in the alpine lotus ( Saussurea nigrescens ) on the Tibetan Plateau by allowing reduced nectar volume provisioning without compromising pollination success. This conclusion is supported by measurements of reproductive and vegetative traits, including nectar, at sites of varying distance from apiaries that have housed introduced honey bees ( Apis mellifera ) since the early 1980s. Nectar volume was more than 60% lower at sites close to apiaries than at more distant sites, while nectar concentration remained consistent. When seedlings from field sites were grown under common garden conditions, trends in nectar volume identical to those in the field were observed, indicating that recently evolved genetic differences likely underlie patterns observed in the field. The adaptive advantage of reduced nectar volume under high pollinator density was clear in both the field and in the common garden. Specifically, plants from sites close to apiaries were taller, had more aboveground biomass, and produced more flowers and seeds compared to those at distant sites, which is consistent with the tradeoffs between nectar volume per flower and flower number per inflorescence within sites. The evolution of reduced nectar volume suggested by our results shows that the widespread practice of beekeeping might be a strong selective agent acting on wild plant populations and illustrates that human activities may indirectly affect evolution by changing critical species interactions.

Simultaneous determination of 30 hormones illegally added to anti-ageing functional foods using UPLC-MS/MS coupled with SPE clean-up - Xiaoqin He; Cunxian Xi; Bobin Tang; Guomin Wang; Dongdong Chen; Tao Peng; Zhaode Mu (Food Additives & Contaminants: Part A, 2014)

MiR-506 inhibits PRRSV replication in MARC-145 cells via CD151 - Junjing Wu; Xianwen Peng; Ao Zhou; Mu Qiao; Huayu Wu; Hongwei Xiao; Guisheng Liu; Xinmin Zheng; Shujun Zhang; Shuqi Mei (Molecular and Cellular Biochemistry, 2014)

Occurrence and particle-size distributions of polycyclic aromatic hydrocarbons in the ambient air of coking plant - Xiaofeng Liu; Lin Peng; Huiling Bai; Ling Mu; Chongfang Song (Environmental Geochemistry and Health, 2014)

Clinical and laboratory characteristics of patients having amyloidogenic transthyretin deposition in osteoarthritic knee joints - Ya-Jun Gu; Peng Ge; Yun Mu; Jin-Hai Lu; Fang Zheng; Xu-Guo Sun (Journal of Zhejiang University-SCIENCE B, 2014)

An Informetric Profile of Water Resources Management Literatures - Jun-Lin Ren; Peng-Hui Lyu; Xin-Mu Wu; Fei-Cheng Ma; Zhi-Zhang Wang; Gang Yang (Water Resources Management, 2013)

Identification of the promoter region and genetic mutations of the porcine GALP gene - Lina Su; Shuqi Mei; Hu Tao; Xianwen Peng; Xiaojie Sun; Huayu Wu; Xuying Zhang; Mu Qiao; Fenge Li (Molecular Biology Reports, 2013)

OsPFA-DSP1, a rice protein tyrosine phosphatase, negatively regulates drought stress responses in transgenic tobacco and rice plants - Bing Liu; Jieqiong Fan; Yang Zhang; Peiqiang Mu; Peng Wang; Jianbin Su; Huihuang Lai; Shaowu Li; Dongru Feng; Jinfa Wang; Hongbin Wang (Plant Cell Reports, 2012)

De novo characterization of the root transcriptome of a traditional Chinese medicinal plant Polygonum cuspidatum - DaCheng Hao; Pei Ma; Jun Mu; ShiLin Chen; PeiGen Xiao; Yong Peng; Li Huo; LiJia Xu; Chao Sun (Science China Life Sciences, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Random-walk model simulation of air pollutant dispersion in atmospheric boundary layer in China - Peng Wang; Hailin Mu (Environmental Monitoring and Assessment, 2011)

Sequence characterization and promoter identification of porcine APC10 gene - W. B. He; Z. W. Wang; Y. Li; Z. L. Tang; S. L. Yang; Y. L. Mu; K. M. Peng; K. Li (Molecular Biology Reports, 2010)

Trend and change-point analyses of streamflow and sediment discharge in the Yellow River during 1950–2005 - Peng Gao; Xunchang Zhang; Xinming Mu; Fei Wang; Rui Li; Xiaoping Zhang (Hydrological Sciences Journal, 2010)

Partial molecular characterization, expression pattern, polymorphism and association analysis of porcine SKP2 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. M. Peng; K. Li (Molecular Biology Reports, 2010)

Expression and SNP association analysis of porcine FBXL4 gene - Y. Li; S. L. Yang; Z. L. Tang; W. T. Cui; Y. L. Mu; M. X. Chu; S. H. Zhao; Z. F. Wu; K. Li; K. M. Peng (Molecular Biology Reports, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Mitochondrial DNA sequence polymorphisms of five ethnic populations from northern China - Qing-Peng Kong; Yong-Gang Yao; Mu Liu; Shu-Ping Shen; Cai Chen; Chun-Ling Zhu; Malliya Gounder Palanichamy; Ya-Ping Zhang (Human Genetics, 2003)